Succinic acid production from pineapple-derived waste within a biorefinery framework: A review of technological approaches, process integration, and technology readiness - Ningsi Lick Sangadji; Dwini Normayulisa Putri; Ibnu Maulana Hidayatullah; Meka Saima Perdani; Kristina Violeta; Nayla Tifana Fillah (Biomass and Bioenergy, 2027)

Starch structure-function relationships and modified starch requirements for applications in dairy analogues: Molecular insights, modification impacts, and applications - Saima Nigar; Praveen Kumar Sappati; Kadavakollu Subrahmanyam; Gourav Dhar Bhowmick (Food Hydrocolloids, 2026)

Evaluation of gene markers invA, phsB, and tviA for detection of Salmonella Typhi by SYBR Green TM real-time PCR assay in clinical samples - Muhammad Luqman Qadir; Samreen Arshad; Nazim Hussain; Saima Younas; Rabia Arooj; Ahmer Bin Hafeez (Molecular Biology Reports, 2026)

Evaluating the presence of bovine coronavirus in diarrheic calves in Lahore, Punjab, Pakistan: a food security risk - Saima Abbas; Shahan Azeem; Sohail Raza; Sehrish Firyal (Brazilian Journal of Microbiology, 2026)

A pixel-based integrated multi-hazard coastal vulnerability framework for the Eastern and Southern Coasts of Peninsular Malaysia - Saima Khurram; Amin Beiranvand Pour; Milad Bagheri; Effi Helmy Ariffin; Mohd Fadzil Akhir; Saiful Bahri Hamzah (Ocean & Coastal Management, 2026)

Green synthesis of biomass derived zinc-ferrite bimetallic nanoparticles and their catalytic applications to access bioactive nitrogenous heterocyclic scaffolds - Ekta Bala; Ankit Kachore; Varun Aggarwal; Hemant Singh; Ishika Sharma; Himanshu; Rohit Sharma; Saima; Rakesh Kumar; Kasim Sakran Abass; Praveen Kumar Verma (Journal of Environmental Chemical Engineering, 2026)

Hydraulic reconstruction and geomorphological impacts of surge-induced GLOFs in the Upper Indus Basin - Saima Ali; Sajid Ali; Lei Wang; Sidra Batool; Xiuping Li; Jharana Nepal (Journal of Hydrology, 2026)

High-performance NiFe₂O₄/poly-L-cysteine nanocomposite for efficient detection of heavy metals in food samples - Shakoor Ahmed Solangi; Ayşen Höl; Aydan Elçi; Şükrü Gökhan Elçi; Jameel Ahmed Baig; Saima Perveen (Food Chemistry, 2026)

Elevated Carbon Dioxide Modifies Root Metabolic Activities and Sustains Wheat Grain Yield Under Drought Stress - Aneela Ulfat; Saima Ashraf; Habib Ali; Aasma Noureen; Sadaf Kayani; Imran Haider Shamsi (Journal of Soil Science and Plant Nutrition, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Remote sensing for Antarctic geological mapping: Evidence, validation challenges and future directions - Khurram Riaz; Amin Beiranvand Pour; Aidy M. Muslim; Saima Khurram; Adel Shirazy; Aref Shirazi; Jabar Habashi; Basem Zoheir; Mazlan Hashim; Sareh Sadigh (Remote Sensing Applications: Society and Environment, 2026)

Supporting Healthy Aging in Illinois: A Needs Assessment of Social Connectedness, Nutrition, and Physical Activity Resources Among Older Adults - Tracy Bowden; Progati Bakshi; Emily Harmon; Rachel Mannen; Krystal Hodge; Saima Hasnin (Journal of Nutrition Education and Behavior, 2026)

Correlates of Children’s Plate Waste in Early Care and Education Settings: A Systematic Review - Progati Bakshi; Krystal Hodge; Justine Karduck; Sarah C. Williams; Saima Hasnin (Journal of Nutrition Education and Behavior, 2026)

Meeting Child and Adult Care Food Program Meal Patterns May Not Ensure Healthier Snack Menus in Family Child Care Homes - Progati Bakshi; Susan B. Sisson; Divya Patel; Alicia L. Salvatore; Saima Hasnin (Journal of Nutrition Education and Behavior, 2026)

Biodiesel production from discarded fish waste lipids using CaO-based heterogeneous catalyst: kinetics modeling, process optimization and validation using Artificial neural network - Umrana Maheer; Md Mokarram Badsha; Fatin Najwa Joynal Abedin; Venugopal Balakrishnan; Saima Sohni; Muzafar Zulkifli; Anita Ramli; Md Sohrab Hossain (Biomass and Bioenergy, 2026)

Nanopriming with biogenic selenium nanoparticles restores physiological performance and antioxidant defense in salt-stressed maize cultivars - Hummera Nawaz; Amina Ameer; Ameer Khan; Anees Manzoor; Muhammad Jamil; Saima Shafique; Ansar Mehmood; Khawaja Shafique Ahmad (Biocatalysis and Agricultural Biotechnology, 2026)

Mechanistic insights into profenofos interactions with antioxidant enzymes in Labeo rohita - Saima Naz; Jhan Zeb; Urwah Ishaque; Ahmad Manan Mustafa Chatha; Ghulam Abbas; Ghazi Alatawi; Saba Iqbal (Aquatic Toxicology, 2026)

Green Synthesis of a ZnO@Sorghum Nano-Bioadsorbent for Enhanced Dye Wastewater Treatment - Muhammad Arslan Khalil; Bushra Sadia; Saima Noreen; Faisal Saeed Awan; Azeem Iqbal Khan; Muhammad Asif; Bilal Ahmad (Water, Air, & Soil Pollution, 2026)

Photocatalytic Degradation of Pesticides Employing Metal-doped and Graphene-interfaced Semiconductor Nanocomposites: Advantages, Mechanism and Affecting Parameters - Saima Khan Afridi; Khalid Umar; Mohd Rizal Razali; Waseem Raza (Water, Air, & Soil Pollution, 2026)

Temporal Profile of Soluble TLR4 and its Association with Intracerebral Haemorrhage Expansion - Maria Lucas-Parra; Carme Gubern-Mérida; Sofia Dávila; Tomàs Xuclà-Ferrarons; Joan Martínez; Saima Bashir; Alan Murillo; Víctor Vera-Monge; Juan Álvarez-Cienfuegos; Laia Carballo-Perich; Elisabet Ortiz; Isabel Vielba-Gomez; et al. (Translational Stroke Research, 2026)
Inflammation contributes to haematoma expansion (HE) and poor prognosis in spontaneous intracerebral haemorrhage (ICH). This study aimed to characterise the temporal profile of soluble Toll-like receptor 4 (sTLR4) during the hyperacute and acute phases of ICH and to evaluate its association with HE. Serum sTLR4 levels were measured at admission, 24 and 72 h from 99 patients with primary hemispheric ICH within 12 h of symptom onset, and at baseline from 39 non-stroke controls using enzyme-linked immunosorbent assay (ELISA). Longitudinal sTLR4 fluctuations were evaluated through linear mixed-effects models. Independent HE prognosticators were identified using multivariable logistic regression, and model performance was assessed via the area under the receiver operating characteristic curve (AUC-ROC). ICH patients exhibited significantly higher baseline sTLR4 levels than controls, which declined over time and were not associated with clinical variables. Notably, patients with HE demonstrated higher admission sTLR4 levels than those without HE (2.50 [95% CI: 1.84–3.16] vs. 1.62 [95% CI: 1.22–2.02] ng/mL, p = 0.027). Furthermore, while the non-HE group showed a rapid decrease within the first 24 h, the HE group maintained elevated levels with a more gradual decline. A multivariable model incorporating baseline ICH volume and sTLR4 levels achieved an AUC of 0.829, with positive and negative predictive values of 70.8% and 90.1%, respectively. These findings suggest that TLR4 may be involved in the pathophysiology of HE, and the combination of baseline ICH volume and sTLR4 levels could serve as a useful tool to stratify patients into low- and high-risk groups for HE.

Non-coding RNAs as central regulators of phytohormone signaling in plant abiotic stress responses - Sajid Ali Shah; Alisa Chowhan; Saima Aslam (Plant Molecular Biology, 2026)

Formulation and Evaluation of Losartan Potassium Microparticles Loaded Controlled-Release Tablets: An In-Vitro Perspective - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Farman Shah; Naveed Ullah; Fida Muhammad; Anam Adil; Sami ul Haq; Haroon Khan (Journal of Pharmaceutical Innovation, 2026)

Mechanistic insight into anti-inflammatory activity of Fagonia cretica via COX inhibition and multimodal pharmacological evaluation - Iqra Farzeen; Zunaira Jaan; Saima Muzammil; Asma Ashraf (Inflammopharmacology, 2026)

Combined Effects of Isolation by Distance, Ecology and Resistance on Population Genetic Divergence in Rana kukunoris From Qinghai‐Tibetan Plateau - Huan Xiong; Hongzhou Chen; Yan Ma; Xueyan Liu; Yanfang Wu; Samra Saima; Shaofei Yan; Haifen Qin; Zhenkun Zhao; Jiahong Liao; Liqing Peng; Min Tang; et al. (Molecular Ecology, 2026)
Investigation of the impact of ecological and landscape processes on genetic population structuring and differentiation is critical for understanding adaptation to different environments. Several hypotheses, including isolation by distance (IBD), isolation by environment (IBE) and isolation by resistance (IBR), have been proposed to explain the spatial patterns of genetic diversity and differentiation among populations. However, these hypotheses have rarely been tested together, and the relative importance of these processes is still unclear. Here, we employed genome‐wide SNP data to investigate the genetic structure of 32 Rana kukunoris populations from the Qinghai‐Tibetan Plateau and explored the patterns and extent of genetic divergence among these populations in relation to the three aforementioned isolation patterns. The results indicated that the species was genetically highly structured ( F st values ranging from 0.03 to 0.80) and composed of three distinct lineages, with a high level of gene flow between the eastern lineage and the other two lineages (southern and western). Geographic isolation, environmental isolation and landscape resistance have all significantly influenced genetic differentiation among populations, as indicated by Mantel tests, suggesting that all three processes (viz. IBD, IBE and IBR) have shaped the degree of genetic differentiation. Variance partitioning (Varpart4) showed that IBD accounted for most of the variance (16.8%), followed by IBR (4.1%) and IBE (3.2%). The three most important environmental factors influencing genetic divergence among R. kukunoris populations, identified through multiple regression on distance matrices (MRM), were the occurrence of saline–alkali soil, road proximity and altitude. Interestingly, the relative contributions of isolation hypotheses varied regionally: MRM and varpart4 analyses revealed that IBE dominated in the north (85.2%), shaped by rivers and precipitation; IBR was strongest in the east (23.0%), driven by rivers, road proximity and distance; while IBD prevailed in the south (8.5%). These findings provide novel insights into the different factors and their relative importance in shaping the degree of genetic differentiation in high‐altitude amphibians.

Retraction Note: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2026)

Radiomic correlates with overall survival in glioblastoma: amide proton transfer (APT) imaging-based feature analysis and integration of clinical factors - Saima Safdar; Nathaniel Barry; Michael Bynevelt; Adriano Polpo; Suki Gill; Pejman Rowshanfarzad; Martin A. Ebert (Physical and Engineering Sciences in Medicine, 2026)
This study identifies amide proton transfer (APT) imaging radiomic features that correlate with glioblastoma survival and explore the relationship of combined radiomic data and biomarkers such as age and MGMT methylation status to survival prognosis. In a retrospective study of 66 glioblastoma patients (2022–2023), SlicerBrats was used for automatic tumor segmentation and 504 radiomic features were extracted from APT images. A two-step feature reduction process was applied: (1) Pearson correlation reduced the features to 59 by mitigating multicollinearity, and (2) a Cox model with best subset selection identified the optimal features using the lowest Akaike Information Criterion (AIC). The Goodness-of-Fit (GOF) test was used to evaluate model adequacy. Bootstrapping with 1000 iterations was used to compute the confidence interval for the concordance index (C-index). Univariate Cox models assessed individual radiomics, while models with multiple features evaluated radiomics alone, with age, MGMT methylation, and both. Kaplan-Meier and log-rank tests were performed to stratify survival groups. The radiomics-only model showed the highest C-index (0.74), AIC (191.35), and GOF ( p < 0.005). Adding age maintained the C-index (0.74) but raised AIC to 193.16 ( p = 0.01). The radiomics + MGMT model achieved a C-index of 0.73 and the lowest AIC (190.15). Kaplan-Meier curves and log-rank tests confirmed all models significantly distinguished survival groups ( p < 0.05). APT-derived radiomic features, especially from edema and necrosis, correlate with glioblastoma survival time. Adding MGMT methylation improved predictive accuracy, achieving the lowest partial AIC and a C-index of 0.73. Further validation in larger cohorts is recommended.

Novel Hybrid Material as a Robust Photocatalyst for Degradation of Aqueous Phenolic Contamination - Bushra Bostan; Saima Sadiq; Inam Ullah; Makkah Zaman; Mian Muhammad; Muhammad Sadiq (Water, Air, & Soil Pollution, 2026)

Assessment of Cadmium in Water, Sediment, and Fish of Baraila Wetland, Bihar, India - Saima Anjum; Mohammed Aasif Sulaiman; Mohammad Masroor Zafar; Divya; Anupma Kumari (Water, Air, & Soil Pollution, 2026)

Host-derived Probiotics Enhance Immune Response and Gut Microbiome in the Freshwater Prawn Macrobrachium rosenbergii - Ayesha Akhter Sumona; Md. Belal Hossen; Saima Binte Hadi; Md. Amdadul Haque; Md. Nurul Haider; Muhammad Tofazzal Hossain; Md Samsul Alam (Probiotics and Antimicrobial Proteins, 2026)

First Comprehensive Assessment of Cytochrome P4501A Response of Common Carp (Cyprinus Carpio, Linnaeus 1758) with the Nutrient Enrichment in Different Freshwater Lakes of North-Western Himalayas - Saima Andleeb; Azra Shah; Durdana Qazi; Asim Iqbal Bazaz; Irfan Ahmad Bhat; Mohd Ashraf Rather; Oyas Asimi; Rashid Ahmad Shah; Irfan Ahmad Khan (Bulletin of Environmental Contamination and Toxicology, 2026)

Multi-Species Probiotics Improve Health Performance and Alleviate Stress Responses of Rohu (Labeo rohita) in Inland Brackish Water Ponds - Habiba Jamil; Abdul Ghaffar; Fozia Afzal; Saima Naz; Ayesha Farooq; Maria Saeed Khan; Fuad M. Alzahrani; Khalaf F. Alsharif; Khalid J. Alzahrani; Qudrat Ullah (Probiotics and Antimicrobial Proteins, 2026)

Poly 3-hydroxybutyrate production from corncobs fortified with sugarcane molasses: optimization and recovery strategies - Sikander Ali; Muhammad Arshad; Sibtain Ahmed; Saima Shahzad Mirza; Khayala Mammadova; Muhammad Usman Ahmad; Yousaira Masud (World Journal of Microbiology and Biotechnology, 2026)

Synthesis of oleanonic acid derivatives and evaluation of their biological activities - Zareena Kiran; Sabira Begum; Sara Sara; Bina S. Siddiqui; Talea Sana; Syed Tahir Ali; Hafiz Nadeem Khan; Saima Rasheed; M. Iqbal Choudhary; Sammer Yousuf; Memoona Bibi; Ayaz Ahmed; et al. (Natural Product Research, 2026)

Palmitic acid in cancer research: mechanistic insights from in vitro and in vivo studies - Muhammad Muzammil Nazir; Sehrish Muzaffar; Saima Muzammil; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Behavioral, Hematological, Biochemical, Antioxidant, Histopathological and Micronuclear Abnormality in the Erythrocytes of Ctenopharyngodon idella Exposed to Chromium Chloride Toxicity - Saima Naz; Ahmad Manan Mustafa Chatha; Khalid J. Alzahrani; Khalaf F. Alsharif; Fuad M. Alzahrani; Qudrat Ullah; Nimra Amjad; Haseeb Khaliq; Riaz Hussain (Biological Trace Element Research, 2026)

High-throughput detection, dietary exposure assessment, and producing Fungi of 16 masked mycotoxins in dried longan in Asia - Hao Deng; Zunyu Chu; Surat Hongsibsong; Tariq Ismail; Saima Perveen; Yunkai Gao; Yingliang Ge; Qingchun Yin (Food Research International, 2026)

Synthesis of Novel Bentonite Composites for Enhanced Remediation of Basic Fuchsin Dye - Ayesha Naseer; Ruba Munir; Gadah Albasher; Muhammad Husnain Manzoor; Murtaza Sayed; Faheem Abbas; Saima Noreen (Water, Air, & Soil Pollution, 2026)

Immunopharmacological effects of shikonin in experimental rheumatoid arthritis: a systematic review and meta-analysis of in vivo studies - Muhammad Muzammil Nazir; Saima Muzammil; Muhammad Mujammil Nazir; Sara Nazir; Asma Ashraf (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Antidepressant and memory-improving effects of zinc oxide-catechin nanocomposites following d-galactose administration in rats - Noreen Samad; Natasha Manzoor; Bilal Saqlain; Saima Khaliq (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Fabrication and In-Vitro Evaluation of Floating Tablets of Levofloxacin Hemihydrate for the Local Treatment of Helicobacter Pylori Infection - Abdullah Khan; Asif Nawaz; Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Haroon Khan; Muhammad Musa Khan; Irum Farooq; Saima Mahmood (Journal of Pharmaceutical Innovation, 2026)

Fabrication, Preparation and In-Vitro and In-Vivo Evaluation of Metoprolol Tartrate Controlled-Release Matrices to Establish a Correlation - Kamran Ahmad Khan; Ashfaq Ahmad; Muhammad Israr; Saima Mahmood; Sami-ul-Huq; Naveed Ullah; Anam Adil; Fida Muhammad (Journal of Pharmaceutical Innovation, 2026)

Allelopathy: A Natural Approach to Weed Management - Mo Shadab; Farha Aijaz; Nazish Akhtar; Quratul-ain; Saima Malik; M. B. Siddiqui (Journal of Crop Health, 2026)

Anti-inflammatory role of metal and metal oxide nanoparticles: a review of toxicity, green synthesis, and immunomodulatory mechanisms - Rimsha Ashraf; Shaukat Ali; Muhammad Summer; Saima Riaz; Amina Iqbal; Ramzana Bibi; Haiqa Shabbir (Inflammopharmacology, 2026)

Constructing an in-situ Fenton reaction using iron-air fuel cells with a graphite cathode for landfill leachate treatment - Sizhuo Wan; Cong Ding; Bingyin Liu; Mahmood Qaisar; Bibi Saima Zeb; Ru Wang; Linjiang Yuan (ENGINEERING Environment, 2026)

Comparative Performance of Different Plants as Phytoremediators for Heavy Metals Released by Varying Density Road Traffic in District Malakand, Pakistan - Saima Ajmal; Maria Sadia; Muhammad Zahoor (Bulletin of Environmental Contamination and Toxicology, 2026)

Red-emissive carbon dot (RCDs@Ag+) nanohybrid as a dual-functional platform for glutathione sensing and antibacterial applications - Farid Ahmed; Saima Hameed; Muhammad Muzammal Hussain; Jiarong Nan; Hai Xiong (Analytica Chimica Acta, 2026)

Carbon-based nanomaterials in aquatic environments: sources, fate, toxicological effects, and risk profiling with special reference to aquaculture systems - Saba Khursheed Khan; Saima jan; Shafiya Mushtaq; Hudisa banoo; Joydeep dutta; Irfan Ashraf Badroo; Ishtiyaq Ahmad; Mohd Ashraf Rather (Aquaculture International, 2026)

Associations of antihypertensive, antidiabetic, and antihyperlipidemic medications with cognitive performance in an Asian population - Lam-Quang Nguyen; Xiangyuan Huang; Wei Ying Tan; Baizura Binte Abu Bakar; Jiannan Huang; Narayanaswamy Venketasubramanian; Saima Hilal (GeroScience, 2026)

Buoyant calcium stearate modified sorbent based on Rhizoclonium hookeri derived activated carbon for facile oil spill clean-up - Saima Rehman; Esraa M. Bakhsh; Sher Bahadar Khan; Md. Sohrab Hossain; Mehreen Zada; Nouman Khan; Shahid Ali Khan; Saima Sohni (Environmental Science and Pollution Research, 2026)

Transplantation of Ru265-treated mitochondria enhances the therapeutic impact on skeletal muscle ischemia-reperfusion injury - Saima Barki; Fazal Wahid; Shafia Khan; Laiba Tariq Abbasi; Zarrish Rubab; Ameer Hamza; Farman Ullah; Khadeeja Ahsan; Durre Shehwar; Muhammad Rizwan Alam (Molecular and Cellular Biochemistry, 2026)

When the Lunchbox Meets the Algorithm: AI’s Next Chapter in Children’s Nutrition Education - Padideh Lovan; Saima Hasnin; Shanté Jeune; Lisa Larsen; Lynn Fredericks (Journal of Nutrition Education and Behavior, 2026)

Protective potential of linalool against cyclophosphamide-induced interstitial cystitis: mechanistic insights from experimental and computational approaches - Irfan Anjum; Asfia Arooje; Saima; Fawad Naeem; Muhammad Naveed Mushtaq; Kashif Barkat; Zaka Ur Rehman; Syed Damin Abbas Hamdani; Shah Jahan; Mohammed Dauelbait; Amir Bouallegue; Esmael M. Alyami; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Expression of asprosin and OLFR734 in reproductive tissues of polycystic ovary syndrome mice: insights into metabolic and reproductive dysfunction - Sana Khan; Saima Syeda; Anju Shrivastava (Cell and Tissue Research, 2026)

Dual benefits of rapid changes in male amphibian body color during the breeding period: sexual selection and anti-predator benefits - Hongzhou Chen; Huan Xiong; Jingyu Xia; Xueyan Liu; Yanfang Wu; Yan Ma; Jingyi Zhang; Xingyue Hu; Samra Saima; Wei Chen (Behavioral Ecology and Sociobiology, 2026)

Molecular insights into HPV-16 L2 capsid protein and inhibitor screening study - Saima Younas; Atiqa Nosheen; Muhammad Abdul Qayyum; Hafiza Ayesha Malik; Sadia Manzoor; Rabia Arooj; Nazim Hussain; Qurban Ali; Muhammad Arshad Javed; Daoud Ali; Adnan Iqbal (In Silico Pharmacology, 2026)

Membrane distillation crystallization: From mechanisms and process control to sustainable production of tailored crystalline materials - Lebea N. Nthunya; Aftab Ahmad Khan; Libing Zheng; Mookgo Mofokeng; Qiyang Wu; Timothy O. Ajiboye; Subhendu Dhibar; Mantoa Sekota; Mosotho J. George; Saima Farooq; Bart Van der Bruggen; Bhekie B. Mamba; et al. (Journal of Water Process Engineering, 2026)

Fabrication of Graphene Oxide-Cobalt Ferrite Nanocomposites for the Remediation of Organic Pollutants from Aqueous Solution: Kinetics, Isotherms, Thermodynamics, and Regeneration Aspects - Abid Ullah; Tahira Mahmood; Rahmat Ali; Saima Momin (Water Conservation Science and Engineering, 2026)

Retraction Note: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2026)

Molecular Characterization of Oculocutaneous Albinism in Consanguineous Pakistani Families: Unraveling Disease-Causing Pathogenic Variants in OCA2 and TYR Genes for Precision Diagnosis - Haiba Kaul; Shagufta Naz; Hafiz Ishfaq Ahmad; Nameerah Saleem; Muhammad Shakil; Sabika Firasat; Bilal Majeed; Saima Sharif; Farzana Rashid; Abdullah Etezaz; Muhammad Umer Khan (Biochemical Genetics, 2026)

Silver nanoparticles in water disinfection: a comprehensive overview on their mechanisms, benefits, and limitations - Muhammad Shehroz Zafar; Sana Ejaz; Farhan Ahmad; Ahmad H. Ibrahim; Sawsan S. Al-Rawi; Faiza Manzoor; Sadia Aziz; Saima Iqbal; Muhammad Adnan Iqbal (Archives of Microbiology, 2026)

Molecular adaptations of the estuarine fish Etroplus suratensis in response to salinity fluctuations - M. A. Pradeep; Saima Rehman; Irine Maria Jose; T. V. Arun Kumar; Vinaya Kumar Katneni; Adnan Hussain Gora; N. R. Dhanutha; Ashok Kumar Jangam; T. S. Azhar Shahansha; K. K. Vijayan (Frontiers in Marine Science, 2026)
Climate-driven shifts in salinity regimes pose significant challenges to aquatic organisms, particularly those inhabiting dynamic coastal ecosystems. Etroplus suratensis (Pearl spot), a euryhaline cichlid capable of thriving across fresh, brackish, and marine environments, offers an excellent model for understanding molecular strategies underpinning salinity acclimation. This study investigated the transcriptomic reprogramming in the gills of fish acclimated for 21 days to freshwater (0‰), brackish water (18‰), and marine water (36‰) conditions. Freshwater exposure elicited a coordinated metabolic response characterized by activation of mitochondrial energy pathways, including oxidative phosphorylation and electron transport, to support ATP-intensive ion uptake, alongside enhanced ion transport functions and epithelial remodeling. In contrast, marine water exposure triggered a more pronounced osmoregulatory shift, with activation of calcium-dependent exocytosis and vesicular trafficking pathways central to maintaining ion balance under high salinity. However, prolonged marine water exposure also led to suppression of key antioxidant and immune pathways, revealing a potential trade-off whereby resources are redirected toward ion regulation at the expense of physiological defense mechanisms. Concurrent enrichment of cortisol synthesis, autophagy, apoptosis, and other stress-responsive pathways further reflects cellular remodeling and adaptive stress management under salinity stress. Collectively, these results demonstrate the remarkable metabolic plasticity and molecular resilience of E. suratensis , highlighting its capacity to deploy distinct, context-dependent mechanisms to maintain homeostasis across fluctuating salinity environments.

Nanotechnology in Parkinson’s Disease: overcoming drug delivery challenges and enhancing therapeutic outcomes - Irfan Ali; Mohammad Adil; Mohammad Imran; Saba Asif Qureshi; Saima Qureshi; Nazeer Hasan; Farhan Jalees Ahmad (Drug Delivery and Translational Research, 2026)

Synthesis, characterization of TiO2/GO nanocomposite and its phocatalytic applications in aqueous medium: A sustainable approach - Hayfa Alajilani Abraheem Jamjoum; Khalid Umar; Saima Khan Afridi; Mohammad Rashid Khan; Rani Rahat (Journal of Water Process Engineering, 2026)

Skin Carotenoid Score Level and Race Affect Intradevice Repeatability of Veggie Meter® at a Single Time Point - Saima Hasnin; Stephanie B. Jilcott Pitts; Charlotte K. Roman; Naiman A. Khan (Journal of Nutrition Education and Behavior, 2026)

Ormosils Fabrication as Adsorbents Projected for Phenol Remediation from Wastewater - Saima Nasreen; Uzaira Rafique; Sana Zulfiqar; Sheryl H. Ehrman; Arshad Ali; Qaisar Mahmood (Water, Air, & Soil Pollution, 2026)

Response surface methodology (RSM) optimization of used engine oil biodegradation by Enterobacter hormaechei NMD and their growth kinetics - Nimra Nisar; Habiba Zaffar; Bibi Saima Zeb; Ghazal Khurshid; Tatheer Alam Naqvi; Mehmoona Zafar; Hajira Haroon (Biodegradation, 2026)

miR-155-SOCS1-Telomere Length Axis: A Tripartite and Multifaceted Approach To Understanding Rheumatoid Arthritis Pathophysiology - Shanza Tariq; Saima Ejaz; Ayesha Liaqat; Sahar Sarwar; Fatma Hussain; Muafia Begum; Farzana Zafar; Zamir Hussain; Saadiya Zia (Cell Biochemistry and Biophysics, 2026)

Molecular docking, dynamics and experimental approach integrated identification of phytopharmaceuticals against methicillin-resistant Staphylococcus aureus (MRSA) infection - Saima; Hitesh K Sharma; S. Latha; Viney Lather; Devesh Tewari; Ruchika Sharma; Gaurav Kumar Jain; Deepti Pandita; Anoop Kumar (Folia Microbiologica, 2026)

Blowin’ in the wind: Onshore winds drive the occurrence of bluebottles (Physalia spp.) at east Australian beaches - Daniel E. Hewitt; Amandine Schaeffer; Jasmin C. Lawes; Sean Kelly; Alistair G.B. Poore; Moninya Roughan; Saima Ajaz; Timothy C. Ingleton; Kylie A. Pitt (Ocean & Coastal Management, 2026)

Seasonal, compositional, and meteorological drivers of PM2.5 oxidative potential: Evidence from a year-long multi-assay study in Melbourne - Saima Iram; Rosemary Fedele; Matthew Mckenzie; Ali Zare; Maja Jovanovic; Svetlana Stevanovic (Science of The Total Environment, 2026)

Roadside dust as a silent threat: Toxic elements contamination and multi-pathway exposure risks in Rangpur City of Bangladesh - Md. Humayun Kabir; Sohana Ferdaus; Sharmin Jahan Saima; Md. Mahbubul Hoque; Rifat Shahid Shammi; Md. Sirajul Islam; Tanmoy Roy Tusher (Next Research, 2026)

Assessment of Chromium Toxicity and Health Risk in Vegetables Grown in Municipal Solid Waste-Amended Soils - Asma Ashfaq; Zafar Iqbal Khan; Toqeer Abbas; Saima Sadaf; Muhammad Arif; Muhammad Fayyaz; Iqra Parvez (Water, Air, & Soil Pollution, 2026)

Synuclein Proteoforms: Role in Health and Disease - Fatima Tu Zahra; Hooreen Kayani; Samra Noreen; Aneeqa Noor; Saima Zafar (Molecular Neurobiology, 2026)

Proteomic Profiling Reveals Mitochondrial Dysregulation in Rapidly Progressive Alzheimer’s: Role of DLDH in Amyloid Beta Aggregation - Saima Zafar; Aneeqa Noor; Neelam Younas; Mohsin Shafiq; Kathrin Dittmar; Oleksandr Yagensky; Matthias Schmitz; Isidre Ferrer; Peter Hermann; Inga Zerr (Molecular Neurobiology, 2026)
Alzheimer’s disease (AD) is presented as multiple clinical variants depending upon the rate of progression and familial background; however, the exact molecular mechanisms associated with these subtypes and their treatments are yet to be understood. The current study is based on a global proteome analysis of brain samples from patients ( n = 38) with rapidly progressive AD (rpAD—survival time < 3 years), sporadic AD (spAD—survival time of 8–10 years), and healthy controls. Proteome analysis revealed a differential regulation of 79 proteins and highlighted the dysregulation of mitochondrial machinery and glucose metabolism in rpAD. Dihydrolipoamide dehydrogenase (DLDH), a mitochondrial oxidoreductase, showed a significant reduction and delocalization in rpAD. In vitro analysis revealed a potential role of DLDH in the aggregation of amyloid beta. Rapid progression in AD may be influenced by the energy homeostasis and redox dysfunction linked with the DLDH.

Integrative Strategies for Enhancing Drought Tolerance in Common Beans: Physiological, Biochemical, and Genetic Perspectives - Saima Fayaz; Ajaz Ahmad Lone; Bilal Ahmad Mir; Zahoor Ahmad Dar; Muneeb Ahmad Rather; Latif Ahmad Peer (Journal of Plant Growth Regulation, 2026)

Hooves, herbs and heritage: ecological insights into the cultural and ethnoveterinary use of Bhagwanpura forest flora in livestock systems - Saima Khalid; Sohaib Muhammad; Ali Ahmad (Genetic Resources and Crop Evolution, 2026)

Molecular docking of nano-curcumin to caspase-3 and caspase-9: Unraveling its cryoprotective mechanism in rabbit sperm extenders - Abdel-Khalek Kh A E.; Saima Qadeer; Sh.A. Gabr; A.M. Shehabeldin; A.E.B. Ghodaia; Sara Latif; Asma Ul Husna (Reproductive Biology, 2025)

Distribution pattern and habitat suitability modelling of an invasive plant species – Solanum viarum Dunal - Saima Jan; Awdhesh Kumar Mishra; Sumreen Amin Shah; Mujtaba Aamir Bhat; Zishan Ahmad Wani; Arif Tasleem Jan (Journal for Nature Conservation, 2025)

Harnessing the potential of thraustochytrids as lipid sources in aquafeeds: a comprehensive review of benefits and challenges - Adnan H. Gora; Viswanath Kiron; Saima Rehman; Sanal Ebeneezar; Chandrasekar Selvam; D.L. Prabu; Qurat ul Ain; K.A. Martin Xavier; Kajal Chakraborty (Bioresource Technology Reports, 2025)

High capacitive polypyrrole-SnO2 nanocomposites anode for the treatment of methyl orange in an integrated photo-electrocatalytic microbial fuel cell - Nishat Khan; Waris; Sayfa Bano; Saima Sultana; Mohammad Zain Khan (Bioresource Technology Reports, 2025)

Fabrication of Green Strontium-Based Perovskites Nanocomposites by Dates Seed Extract for Treatment of Direct Lemon Yellow 44 Dye-Based Wastewater - Maryam Alvi; Ruba Munir; Gadah Albasher; Nazish Jahan; Hina Ambreen; Amna Muneer; Fazila Younas; Raziya Nadeem; Saima Noreen (Water, Air, & Soil Pollution, 2025)

Investigating the Effect of Sn and Pt Doping and Co-doping on the Photocatalytic Efficiency of Zirconia for Degradation of Acid Yellow-76 - Mian Hussain Shah; Saima Sadiq; Umar Wahab; Inam Ullah; Sardar Hussain; Nasr Ullah; Safiullah Khan; Zaffar Iqbal; Muhammad Ismail; Aadil Nabi Chishti; Muhammad Sadiq (Water, Air, & Soil Pollution, 2025)

Climate change and aquatic food systems: fish species shifts, productivity threats, and adaptive pathways - Bushra Irfan; Saima Naz; Ahmad Manan Mustafa Chatha; Sobia Malik; Urwah Ishaque; Saba Iqbal (Theoretical and Applied Climatology, 2025)

Genetic Mechanisms and Improvement Strategies for Rice Sheath Blight Resistance - Muhammad Usama Younas; Bisma Rao; Muhammad Qasim; Irshad Ahmad; Zhiming Feng; Saima Parveen Memon; Rashid Iqbal; Shimin Zuo (Plant Molecular Biology Reporter, 2025)

Platelets and mitochondria: the calcium connection - Durre Shehwar; Saima Barki; Alessandro Aliotta; Debora Bertaggia Calderara; Lucas Veuthey; Cindy Pereira Portela; Lorenzo Alberio; Muhammad Rizwan Alam (Molecular Biology Reports, 2025)

Impact of lipids modulation on growth, histology, structural integrity, and thermo-biochemical profile of Cyprinus carpio fry - Umar Farooq; Imrana Amir; Hira Bukhat; Saima Nousheen; Usama Saleem; Juan Pedro Luna-Arias; Luis Edwardo Palomo Martínez; Gabriela Medina-Pérez; Armando Pelaez-Acero; Amir Ali (Fish Physiology and Biochemistry, 2025)

Innovative technology and emerging trends in sustainable aquaculture: a road to increase output and environmental resilience - Saima Naz; Saba Iqbal; Urwah Ishaque; Ahmad Manan Mustafa Chatha (Aquaculture International, 2025)

Loliolide: green monoterpenoid lactone with therapeutic and ecological significance-a comprehensive review with computational validation - Iqra Farzeen; Saima Zafar; Nimrah Zafar; Sehrish Fatima; Muhammad Muzammil Nazir; Asma Ashraf (Molecular Diversity, 2025)

Comparative study of extraction methods and process parameters of polyphenolic content obtained from Celosia argentea L. Flower for herbal sunscreen - Humaira Arshad; Adnan Afzal; Arifa Mehreen; Faiza Shakoor; Valisher Sapayev Odilbek Uglu; Saima Qadeer; Samiyah Tasleem; Rana Muhammad Kamran Shabbir; Mukhayya Djumaniyazova (Natural Product Research, 2025)

Secondary droplet breakup of impaction-pin nozzle: Comparison between experimental and CFD-DPM modelling - Saima Bukhat Khan; Joel Alroe; Chris Medcraft; Emilie Sauret; Daniel Harrison; Zoran Ristovski (Journal of Aerosol Science, 2025)

Using indoor CO2 concentration thresholds to understand and improve the air quality of public buildings: A practical approach - Henry P. Oswin; Lucien Glachant; Savinda Arambawatta Lekamge; Behnaz Alinaghipour; Saima Bukhat Khan; Lidia Morawska (Energy and Buildings, 2025)

Impact of in-ovo dichromatic lights on embryonic growth, hatching performance and welfare traits in commercial layers - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Saima; Hai Lin (Tropical Animal Health and Production, 2025)

Assessing the effect of a yeast product (Pichia guilliermondii) on growth performance, carcass traits, gut morphology, intestinal microbial computation, and immune response in broilers - Noman Khurshid; Saima Naveed; Fazal Raziq; Muhammad Tahir Khan; Assad Ullah (Tropical Animal Health and Production, 2025)

Human health risk of heavy metal biomagnification: Trophic transfer patterns in aquatic ecosystems - Saira Naz; Syed Sikandar Habib; Madeeha Arshad; Saima Majeed; Ümit Acar; Osman Sabri Kesbiç; Mohamed Mohany; Francesca Aragona; Francesco Fazio (Journal of Trace Elements in Medicine and Biology, 2025)

Seasonal Trends in Heavy Metal Pollution and Water Quality in the Chashma (Indus River, Pakistan): A Study on Environmental Health Risks - Saira Naz; Syed Sikandar Habib; Madeeha Arshad; Saima Majeed; Mohamed Mohany (Water, Air, & Soil Pollution, 2025)

Effect of Bioactive Peptides and Encapsulated Butyric Acid on Growth Performance, Gut Health, Immune Status and Nutrient Digestibility in Broiler Chickens - Mohammad Ahmad Qazi; Ehsaan Ullah Khan; Saima Naveed; Shahid Mehmood; Muhammad Muneeb; Muhammad Talha; Muhammad Shabir Shaheen; Sohail Ahmad (International Journal of Peptide Research and Therapeutics, 2025)

Effects of bacteriophage supplementation on performance, gut health and blood biochemistry in broilers challenged with necrotic enteritis - Muhammad Muneeb; Ehsaan Ullah Khan; Saima; Muhammad Suleman; Mian Muhammad Awais; Sohail Ahmad (Research in Veterinary Science, 2025)

Pioneering insights into Lemon basil: High-resolution phytochemical profiling, antioxidant potential, and in-vitro cytotoxic activity against MCF-7 breast cancer cell lines - Pratibha Mishra; Saima Sohrab; Sanjay Kumar Mishra (Next Research, 2025)

Deciphering the accumulation of potentially toxic metals and their relation with size in the five commercially important fish species from the middle stretch of the River Ganga - Mohammed Aasif Sulaiman; Mohammad Masroor Zafar; Divya; Saima Anjum; Kumar Gaurav; Ravindra Kumar Sinha; Anupma Kumari (Next Research, 2025)

Bimetallic nanoparticles loaded on waste derived carbon quantum dots: A green approach for degradation of azo dye - Saima Ameer; Ehab A. Abdelrahman; Fozia Batool; Asifa Batool; Taslim Akhtar; Abdulrahman G. Alhamzani; Mortaga M. Abou-Krisha (International Biodeterioration & Biodegradation, 2025)

Carbon dots: An emerging food analysis nanoprobes for detection of contaminants - Hemant Singh; Saima; Varun Aggarwal; Ankit Kachore; Ekta Bala; Rakesh Kumar; Rohit K. Sharma; Praveen Kumar Verma (Food Chemistry, 2025)

Growth advantage of polyploid Populus ussuriensis driven by root-soil-microbial interactions under nitrogen fertilization - Qingyu Wei; Xing Wei; Saima Khan; Chunze Wu (European Journal of Soil Biology, 2025)

Rice husk-based catalyst for sustainable biodiesel production: A meta-analysis and systematic review - Meka Saima Perdani; Dita Ariyanti; Eko Lela Fitriana; Dwini Normayulisa Putri; Heri Hermansyah (Bioresource Technology Reports, 2025)

Comparative Efficacy of Different Rice (Oryza sativa L.) Genotypes for Improved Zinc and Iron Uptake and Relevant Yield Efficiency under their Foliar Application - Shafiq ur Rahman Memon; Saima Parveen Memon; Muhammad Qasim; Huagang Huang; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Rashid Iqbal; Zicheng Zheng (Journal of Soil Science and Plant Nutrition, 2025)

Developments in deep learning algorithms for coastline extraction from remote sensing imagery: a systematic review - Saima Khurram; Amin Beiranvand Pour; Milad Bagheri; Effi Helmy Ariffin; Mohd Fadzil Akhir; Saiful Bahri Hamzah (Earth Science Informatics, 2025)

Transforming cities from traditional to sustainability: role of electric vehicles and solar photovoltaic energy in decarbonization - Noman Sahito; Muhammad Yousif Mangi; Muhammad Aamir Basheer; Farrukh Baig; Zulfiqar Ali Lashari; Saima Kalwar (Environment, Development and Sustainability, 2025)

Bioactivity of 2-(3,4-Dihydroxyphenyl)-5,7-dihydroxy-2,3-dihydrochromen-4-one from pistacia chinensis on ENPP1 and aldose reductase - Abdur Rauf; Saima Naz; Zuneera Akram; Muhammad Saleem; Taghrid S. Alomar; Najla AlMasoud; Giovanni Ribaudo (Natural Product Research, 2025)

Bergamottin a bioactive compound unveiled: exploring its potential in disease managments and in-silico insights - Iqra Farzeen; Muhammad Muzammil Nazir; Saima Muzammil; Saima Zafar; Derya karatas Yeni; Asma Ashraf (Phytochemistry Reviews, 2025)

Gallic acid alleviates omeprazole-induced depressive behavior and memory impairment - Noreen Samad; Natasha Manzoor; Ali Irfan; Arslan Khalid; Umer Ejaz; Bakar Bin Khatab Abbas; Syed Aun Muhammad; Gamal A. Shazly; Saima Khaliq; Yousef A. Bin Jardan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Prolonged administration of letrozole induces polycystic ovary syndrome leading to osteoporosis in rats: model development and validation studies - Zakiya Usmani; Sheeraz Ahmad; Zeba Usmani; Taru Mishra; Abul Kalam Najmi; Saima Amin; Aayeena Altaf; Showkat Rasool Mir (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Comprehensive Review On the Role of Exogenous Phytohormones in Enhancing Temperature Stress Tolerance in Plants - Sajid Ali Shah; Mohd Arshad; Saima Aslam (Journal of Crop Health, 2025)

Anthropogenic dust pollution influences leaf and root morpho-anatomical traits by altering the metabolism and biochemical properties of indigenous vegetation - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saima Sadaf; Muhammad Kamran; Toqeer Abbas; Shifa Shaffique; Mansour K. Gatasheh (Environmental Geochemistry and Health, 2025)

A review on metallothionein research in marine and estuarine realms: past paradigms and future vistas - Adnan H. Gora; M. P. Sreeram; Saima Rehman; Qurat Ul Ain; Kajal Chakraborty; D. Prema; R. Lavanya; Prabhugouda Siriyappagouder; P. S. Asha (Frontiers in Marine Science, 2025)
Oceans and coastal waters, vital for human survival and climate regulation, are increasingly threatened by heavy metal pollution due to human activities including industrialization and urbanization. Heavy metals including tin, zinc, mercury, copper, nickel, cadmium, cobalt, vanadium, strontium, titanium, arsenic, lead, molybdenum, and chromium are persistent pollutants that can accumulate in marine organisms, posing significant risks to ecosystems and human health. While some heavy metals are essential in trace amounts, they can exert undesirable biological effects at higher concentrations and even become toxic. In response to such toxic exposure, terrestrial and aquatic plants and animals are known to have evolved inherent mechanisms to subdue heavy metal toxicity. These responses often involve the activation of various stress-related proteins, including heat shock proteins, antioxidant enzymes, and metal-binding molecules that work collectively to restore cellular homeostasis. One of the mechanisms to mitigate metal toxicity is through the activity of metallothionein proteins. Metallothioneins, low molecular weight, cysteine-rich proteins, play a crucial role in mitigating the toxic effects of heavy metals. These proteins bind heavy metals, aiding in detoxification, protecting the cells from their undesirable effects, and maintaining metal homeostasis. Thus, metallothionein expression and activity also serve as valuable biomarkers for assessing heavy metal pollution, providing insights into the biological impact of these contaminants. The present review explores the role of bacterial metallothioneins in detoxification and their potential in environmental risk assessment, focusing on their importance in marine species exposed to heavy metal pollution. We explore the studies that report heavy metal contamination in the coastal waters, followed by elucidating the effects of heavy metal exposure on metallothionein activity and expression in marine fish, crustaceans and mollusks. Finally, we provide possible future perspectives of how bacterial metallothioneins can be employed for mitigating ecological damage caused by heavy metals. By understanding the interactions between heavy metals and metallothioneins, we can develop more effective strategies for monitoring and mitigating the effects of heavy metal contamination in marine environments.

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

Determination of heavy metals and morphoanatomical characteristics of the monocots Aristida mutabilis and Cenchrus ciliaris in the dust-contaminated stone crushing industry of Sargodha, Pakistan - Muhammad Asim Sultan; Iftikhar Ahmad; Muhammad Arif; Saud Alamri; Manzer H Siddiqui; Saima Sadaf; Muhammd Kamran (Environmental Monitoring and Assessment, 2025)

Establishing an efficient protoplast isolation and PEG-mediated transformation system for functional genomic studies in Colletotrichum lindemuthianum - Aasiya Nabi; Yogesh Raunta; Rafiq A. Shah; Irtifa Lateef; Zainab Rashid; Naziya Nabi; Tuaha Gowhar; M.D. Shah; I.T. Nazki; Gowhar Ali; Saima Masood; Bilal A. Padder (Physiological and Molecular Plant Pathology, 2025)

Corrigendum to “Smart colorimetric indicator films prepared from chitosan and polyvinyl alcohol with high mechanical strength and hydrophobic properties for monitoring shrimp freshness” [Food Chemistry 445 (2024) 138784] - Jehangir Khan; Haoyue An; Shah Alam; Saima Kalsoom; Shu Huan Chen; Teshale Ayano Begeno; Zhenxia Du (Food Chemistry, 2025)

Lanthanum doped copper ferrite as efficient Electrocatalyst for simultaneous detection of Bentazone and Diuron in vegetable samples - Khalil Akhtar; Jameel Ahmed Baig; Hassan Imran Afridi; Imam Bakhsh Solangi; Saima Perveen; Mohsin Kazi (Food Chemistry, 2025)

Biological potential and therapeutic effectiveness with diverse signaling pathways of phyto-product chicoric acid: a comprehensive review with computational evidence - Muhammad Muzammil Nazir; Iqra Farzeen; Saima Zafar; Sehrish Fatima; Nimrah Zafar; Asma Ashraf; Sogolo Lucky Lebelo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Recombinant production and characterization of novel carboxypeptidase from thermophilic archaeon Thermococcus siculi - Saima Iftikhar; Maida Wahid; Muhammad Shahid Nadeem; Farheen Aslam; Khushi Muhammad (Biologia, 2025)

Critical role of pH in wastewater treatment and resource recovery from the hazardous chemical polishing wastewater - Sizhuo Wan; Sifan Wang; Mahmood Qaisar; Bibi Saima Zeb; Ru Wang; Linjiang Yuan; Ping Zheng (Journal of Water Process Engineering, 2025)

Repurposing and reusing aquaculture wastes through a biosecure microfloc technology - Sayima Majeed Wani; Anayitullah Chesti; Saima Rehman; Vipin Chandra Nautiyal; Irfan Ahmad Bhat; Irshad Ahmad (Environmental Research, 2025)

Phosphate recovery from digested wastewater using electrochemical reactors: Trade-off between efficiency and stability - Sizhuo Wan; Ru Wang; Bibi Saima Zeb; Mahmood Qaisar; Linjiang Yuan; Ping Zheng (Desalination, 2025)

Deciphering the chemical constituents and antimicrobial activity of Prangos pabularia Lindl. using LC-MS/MS in combination with experimental evaluation and computational studies - Aadil Yaseen; Bashir A. Sheikh; Basharat A. Bhat; Saima Hamid; Malik A. Waseem; Mohammed Iqbal Zargar; Manzoor A. Mir; Wajaht A. Shah (Natural Product Research, 2025)

Phytomining potential, micro-morphological assessment, and air pollution tolerance index of plant species in multi-metals contaminated soapstone and crushing stone mines - Tufail Shakeel; Ghulam Mujtaba Shah; Bibi Saima Zeb; Iram Gul; Muhammad Irshad; Habiba Zafar (Science of The Total Environment, 2025)

Energy bandgap tuning of Sr-doped ZnO nanoparticles for photodegradation of azo dyes and antibacterial applications - Hufsa Ahmad; Abu Bakar Siddique; Saima Zaheer; Rabia Sattar; Azhar Abbas; Muhammad Amin; Rashad Al-Salahi; Hatem A. Abuelizz; M. Zubair Saleem (Journal of Water Process Engineering, 2025)

Reduced thermoregulatory ability contributes to increased mortality in urban box turtles (Terrapene spp.) - Stella F. Uiterwaal; Jamie L. Palmer; Saima Farook; Sharon L. Deem; Catherine Taylor; Stephen Blake (Journal of Thermal Biology, 2025)

Sustainable adsorbents: Metal oxide-biochar nanocomposites from Maize Stalks and Wild Tamarind residues for dye removal and phytotoxicity assessment - Ruba Munir; Amna Muneer; Gadah Albasher; Faheem Abbas; Saima Noreen (Groundwater for Sustainable Development, 2025)

Physicochemical, antioxidant and antimicrobial properties of peel, pulp and seeds of different pear cultivars - Saima Gulzar Wani; Fauzia Shafi; Abida Jabeen; Mudasir Ahmad Malik (Food and Humanity, 2025)

KPT-330, A New Candidate Drug for Targeting NOTCH1 Overexpression in T-cell Acute Lymphoblastic Leukemia, An In Vitro and Silico Study - Fariha Naz; Saima Ejaz; Tayyaba Wali; Atiqa Nudrat; Mian Abdur Rehaman Arif; Muhammad Qandeel Waheed; Fatma Hussain; Saadiya Zia (Cell Biochemistry and Biophysics, 2025)

Deep learning model to detect glacial lakes using high-resolution optical and radar satellite images - Sajid Ali; Saima Ali; Lei Wang; Syed Razi Ul Hassan; Garee Khan; Salar Ali; Taimoor Hussain; Dostdar Ali (Remote Sensing Applications: Society and Environment, 2025)

A novel bio-facilitated synthesis of GO/ZnO/Ag nanocomposite via Citrulline Lanatus and OPEFB for enhanced photocatalytic degradation of imidacloprid: Kinetics, mechanism and byproduct analysis - Saima Khan Afridi; Khalid Umar (Journal of Water Process Engineering, 2025)

Extrusion-aided interaction of rice starch with whey protein isolate: Synergistic influence on physicochemical properties and in vitro starch digestibility characteristics - Samar Jan; Tawheed Amin; Syed Zameer Hussain; Abida Jabeen; Mohammad Amaan Seh; Omar Bashir; Sobiya Manzoor; Ufaq Fayaz; Hilal A. Makroo; Saima Wani (Food Chemistry, 2025)

Assessment of flood risk based on CMIP6 for the Northern foothills of Qinling mountain - Adnan Ahmed; HUO Aidi; YANG Luying; ZHAO Zhixin; Saima Q. Memon; Mohamed EL-Sayed Abuarab; Ahmed Elbeltagi (Theoretical and Applied Climatology, 2025)

Therapeutic role of naringin in cancer: molecular pathways, synergy with other agents, and nanocarrier innovations - Abdulsalam Alhalmi; Saima Amin; Tanya Ralli; Khaled Saeed Ali; Kanchan Kohli (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring the bifurcation and stability analysis of the malaria epidemic model and their environmental impacts; a scheme of piecewise modified ABC fractional derivative - Sehrish Ramzan; Saima Rashid; Ilyas Ali; Muzamil Abbas Shah; Nazeran Idrees (Modeling Earth Systems and Environment, 2025)

The First Report of Cod Gill Poxvirus in Gills of Atlantic Cod ( Gadus morhua L.) Suffering From Cardiorespiratory Disease - Mona C. Gjessing; Torstein Tengs; Hanne Nilsen; Saima Mohammad; Simon C. Weli (Journal of Fish Diseases, 2025)
Atlantic cod farming experiences renewed growth in Norway, and increased awareness is essential to address emerging diseases in this species. There are few reports on gill diseases in cod, and to date, no viral gill infections of cod have been documented. In this study, we collected samples from three sequential time points in summer 2023 from farmed cod suffering from cardiorespiratory disease. We document severe heart and gill pathology, and a novel double‐strand DNA virus was discovered in the gills. Through comprehensive genetic characterisation and comparative sequence analysis, this virus was classified as a new species in the genus Poxvirus, designated cod gill poxvirus (CGPV). We demonstrate disease causality with severe gill lesions as shown by histopathology and RNA scope in situ hybridisation, and poxvirus particles were identified in gill epithelial cells by transmission electron microscopy. Further, another gill pathogen not previously described in cod, Candidatus . Branchiomonas cysticola, was identified by pcr and in situ hybridisation. Our findings provide strong evidence for poxvirus in Atlantic cod and underscore the imminent threat posed to Atlantic cod farm industry.

Comparative removal of acid orange 7 and aniline onto mesoporous graphene oxide-nickel ferrite magnetic nanocomposites in batch adsorption and application of conventional kinetic and isotherm models - Abid Ullah; Tahira Mahmood; Rahmat Ali; Saima Momin (Environmental Science and Pollution Research, 2025)

Co-Delivery of Tacrolimus and Thymoquinone Topically by Nanostructured Lipid Carrier Gel for Enhanced Efficacy Against Psoriasis - Meraj Alam; Md. Rizwanullah; Shahnawaz Ahmad; Ashif Iqubal; Showkat R. Mir; Tae-Geum Kim; Saima Amin (AAPS PharmSciTech, 2025)

Effects of different environmental enrichment tools to improve behavior, welfare, and growth performance of broiler chickens - Abdul Ghani; Shahid Mehmood; Faisal Hussnain; Saima (Tropical Animal Health and Production, 2025)

Population Structure and Reproductive Biology of the Pebble Crab, Philyra corallicola (Decapoda: Brachyura: Leucosiidae) off Karachi Coast, Pakistan - Samia Aziz; Saima Siddique; Zarrien Ayub (Thalassas: An International Journal of Marine Sciences, 2025)

Correction: Bioaccumulation of Lead and Mercury in Water, Sediment, and Fish Samples of Baraila Lake, Vaishali, Bihar - Saima Anjum; Anupma Kumari (Biological Trace Element Research, 2025)

Selected regular echinoids (Echinoidea) from the upper Campanian–Maastrichtian along the western borders of the Northern Oman Mountains, with description of a new species - Marouf Abdelaty Mohamed Abdelhamid; Osman Abdelghany; Mahmoud Abu Saima; Anhar Asan (Cretaceous Research, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

Recent advances and factors affecting the adsorption of nano/microplastics by magnetic biochar - Khurram Shahzad; Areej Hasan; Syed Kumail Hussain Naqvi; Saima Parveen; Abrar Hussain; Kyong-Cheol Ko; Sang Hyun Park (Chemosphere, 2025)

RETRACTED ARTICLE: Understanding rice blast: investigating biotechnological methods to speed up the development of robust rice cultivars - Nimra Rajput; Muhammad Usama Younas; Muhammad Qasim; Saima Parveen Memon; Shabana Memon; Magda Abd El-Rahman; Saltanat Aghayeva; Sezai Ercisli; Rashid Iqbal; Shimin Zuo (Genetic Resources and Crop Evolution, 2025)

Bioaccumulation of Lead and Mercury in Water, Sediment, and Fish Samples of Baraila Lake, Vaishali, Bihar - Saima Anjum; Anupma Kumari (Biological Trace Element Research, 2025)

Optimization of Ti3C2T performance through synergistic enhancement of GeO /Ti3C2T heterostructures for ammonium-ion storage - Xinze Zhang; Muhammad Sufyan Javed; Hongjia Ren; Saima Batool; Awais Ahmad; Renqian Tao; Munirah D. Albaqami; Shaukat Khan; Xin Wang; Weihua Han (Chemical Engineering Journal, 2025)

Combating Lead (Pb) Contamination: Integrating Biomonitoring, Advanced Detection, and Remediation for Environmental and Public Health - Saima Zafar; Sehrish Fatima; Farkhanda Asad; Muhammad Muzammil Nazir; Sania Batool; Asma Ashraf (Water, Air, & Soil Pollution, 2025)

Effect of Arsenic Exposure on AS3MT Protein Levels in Serum of Type 2 Diabetic Patients Compared to Non-diabetics - Saima Shokat; Riffat Iqbal; Muhammad Ahmed Ali; Atif Yaqub; Shaista Aslam; Samreen Riaz (Biological Trace Element Research, 2024)

Water quality and stock assessment of Schizothorax niger (Alghad snowtrout) in Manasbal Lake, Kashmir Himalaya - Tabasum Yousuf; Saima Andrabi; Yahya Bakhtiyar (Environmental Monitoring and Assessment, 2024)

Mitigating effects of various phosphorus sources on arsenic toxicity under anaerobic conditions for rice and aerobic conditions for sunflower and maize plants - Mehmet B. TASKIN; Hanife AKCA; Selver KAN; Havva TASKIN; Saima K. BABAR; Yusuf K. KADIOGLU; Kiymet DENIZ; Aydin GUNES (Pedosphere, 2024)

Investigating the potential of 1,2,4-triazoles as corrosion inhibitors for copper and steel: A comprehensive review - Aqsa Ashraf; Naheed Riaz; Saima Muzaffar; Muhammad Atif; Bushra Bashir (Next Research, 2024)

Hybrid entrepreneurship in just transitions: Dealing with dilemmas facing ‘the other’ - Rick Colbourne; Lalarukh Ejaz; Vadim Grinevich; Saima Husain; D'Arcy O'Farrell (Environmental Innovation and Societal Transitions, 2024)

Unveiling the chemical profile, anti-proliferative, pro-apoptotic and anti-migratory effect of Indigofera linifolia in liver and breast cancer cells - Irum Naz; Muhammad Rashid Khan; Saima Ali; Riffat Batool (Biocatalysis and Agricultural Biotechnology, 2024)

Pharmacological and immunomodulatory modes of action of medically important phytochemicals against arthritis: A molecular insight - Aqsa; Shaukat Ali; Muhammad Summer; Saima Yousaf; Laiba Nazakat; Shehzeen Noor (Molecular Biology Reports, 2024)

Inhibition of mitochondrial calcium transporters alters adp-induced platelet responses - Durre Shehwar; Saima Barki; Alessandro Aliotta; Lucas Veuthey; Debora Bertaggia Calderara; Lorenzo Alberio; Muhammad Rizwan Alam (Molecular Biology Reports, 2024)

Unveiling Biochemical Dynamics in Common Bean-Pseudocercospora Pathosystem Under Angular Leaf Spot Pressure in Western Himalayan Kashmir - Aaqif Zaffar; Sadiah Shafi; Samreen Fatima; Ishrat Riyaz; Asha Nabi; Saima Gani; Sajad Majeed Zargar; R. R. Mir; Sajad Nabi; Parvaze A. Sofi (Journal of Crop Health, 2024)

Integrating HRMAS-NMR Data and Machine Learning-Assisted Profiling of Metabolite Fluxes to Classify Low- and High-Grade Gliomas - Safia Firdous; Zubair Nawaz; Rizwan Abid; Leo L. Cheng; Syed Ghulam Musharraf; Saima Sadaf (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Magnetically separable sorbent based on activated carbon derived from a new precursor Rhizoclonium hookeri for facile oil spill clean-up - Saima Sohni; Owais Rashid; Sayyed Hamid Ali; Sher Bahadar Khan; Kalsoom Akhtar; Faryal Mazhar; Md. Sohrab Hossain; Murtaza Sayed; Najeeb Ullah (Algal Research, 2024)

SAR-based oil spill detection and impact assessment on coastal and marine environments - Muhammad Ozair; Muhammad Farooq Iqbal; Irfan Mahmood; Saima Naz (Acta Oceanologica Sinica, 2024)

Surface modification of heterostructured Bi8W4O24/ZrO2@GO composite via low-pressure cold plasma for boosting photocatalytic potential against Basic fuchsin and Bismarck brown Y dyes - Mahwish Iqbal; Haq Nawaz Bhatti; Saima Noreen; Shazia Shukrullah (Environmental Science and Pollution Research, 2024)

Expression of mastitis causing fibrinogen binding protein of gram positive bacteria in genetically engineered switchgrass and antibodies production in mice - Saima Shafique; Nyla Jabeen; Samra Irum; Ansar Mehmood; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2024)

Synthesis of green magnetic hybrid adsorbents and their application for reactive red methyl 4 BL dye removal - Sadaf Gillani; Ruba Munir; Khuram Ali; Muhammad Zeeshan Bashir; Umme Habibah Siddiqua; Saima Noreen (Clean Technologies and Environmental Policy, 2024)

Root endophytic aquatic hyphomycetes from the Nandhaur River, India - Saima Altaf; Saraswati Bisht (Vegetos, 2024)

Assessing Heavy Metal Contamination in Commonly Used Fertilizers for Polyculture Fish Ponds and Its Implications for Human Health: A Comprehensive Investigation - Saira Naz; Madeeha Arshad; Saima Majeed; Sawera Maqaddas; Syed Sikandar Habib; Osman Sabri Kesbiç; Salim S. Al-Rejaie; Mohamed Mohany; Teresa Bottari; Francesca Aragona; Francesco Fazio (Biological Trace Element Research, 2024)

Integrating behavioural, material and environmental science to inform the design and evaluation of a reuse system for takeaway food - Maryam Hoseini; Sarah C. Greenwood; Saima Eman; Paul Mattinson; Harriet M. Baird; Rorie Beswick-Parsons; J. Patrick A. Fairclough; Thomas L. Webb; Anthony J. Ryan; Rachael H. Rothman (Resources, Conservation and Recycling, 2024)

Application of weather post-processing methods for operational ensemble hydrological forecasting on multiple catchments in Canada - Freya Saima Aguilar Andrade; Richard Arsenault; Annie Poulin; Magali Troin; William Armstrong (Journal of Hydrology, 2024)

Alginate-millet starch composite matrices as novel carriers for controlled delivery of grape seed polyphenols: Preparation, characterization, and in vitro release behaviour - Saima Nigar; Kadavakollu Subrahmanyam; Debojit Baidya Choudhury; Khalid Gul; Rachna Sehrawat (Food Structure, 2024)

Green hybrid coagulants for water treatment: An innovative approach using alum and bentonite clay combined with eco-friendly plant materials for batch and column adsorption - Sidra Saqib; Amna Muneer; Ruba Munir; Murtaza Sayed; Muhammad Waqas; Tayyiba Aliyam; Fazila Younas; Mohammad Abul Farah; Mohamed Farouk Elsadek; Saima Noreen (Environmental Research, 2024)

Adsorption-coupled Fenton type reduction of bromate in water by high-yield polymer-derived ceramic-supported nano-zerovalent iron - Muhammad Idrees; Saima Batool; Hina Rasheed; Indika Herath; Jochen Bundschuh; Nabeel Khan Niazi; Mahtab Ahmad; Junguo Xu; Deliang Chen (Environmental Research, 2024)

Lignocellulosic biomass in circular economy: A techno-transition in carbon neutrality towards sustainable energy production - Mudasir Ahmad Bhat; Mujtaba Aamir Bhat; Saima Jan; Ali Asghar Shah; Arif Tasleem Jan (Biomass and Bioenergy, 2024)

Effect of remediation technologies on soil fertility in heavy metal(loid)-contaminated soils: A critical review - Lizhi He; Yan Xu; Mengen Zhang; Saima Gul; Xiaokai Zhang; Huan Zhong; Yanxin Tang; Dubin Dong; Yong Xu; Dan Liu; Nanthi Bolan; Hailong Wang (Critical Reviews in Environmental Science and Technology, 2024)

Reactive Blue MEBF 222 dye and textile wastewater treatment using metal-doped cobalt and nickel perovskites by batch and column adsorption process - Ammara Sherin; Ruba Munir; Nageen Mushtaq; Amna Muneer; Hina Ambreen; Fazila Younas; Mohammad Abul Farah; Mohamed Farouk Elsadek; Saima Noreen (Environmental Monitoring and Assessment, 2024)

Batch and column studies for the removal of basic red-46 dye and textile by using magnesium oxide (MgO), strontium titanium trioxide (SrTiO3), cobalt- and iron-doped lanthanum chromium trioxide (Co.Fe.LaCrO3), and cadmium sulfide (CdS)–doped graphene oxide nanocomposites - Aiman Safdar; Ruba Munir; Zil-E-Hasnain; Saima Noreen (Environmental Science and Pollution Research, 2024)

Impact of nitrogen fertilization and spacing on the yield and oil content of scented geranium (Pelargonium graveolens L’Hér.) - Tuybia Bilal; Tawseef Ahmad Mir; Muatasim Jan; Benatul Behar; Ishrat Nazir; Saima Farooq; Bilkees Ayoob (Vegetos, 2024)

Inflammatory response of nanoparticles: Mechanisms, consequences, and strategies for mitigation - Muhammad Summer; Rimsha Ashraf; Shaukat Ali; Horacio Bach; Shehzeen Noor; Qudsia Noor; Saima Riaz; Rana Rashad Mahmood Khan (Chemosphere, 2024)

Spatiotemporal distribution, ecological risk assessment, and human health implications of currently used pesticide (CUP) residues in the surface water of Feni River, Bangladesh - Ananya Bhuiya; Sabina Yasmin; M. Golam Mustafa; Md Aftab Ali Shaikh; Jerin Saima; Mohammad Moniruzzaman; Md Humayun Kabir (Science of The Total Environment, 2024)

Farm to fork strategy for evaluating the qualitative and quantitative health risks to the Nepalese population associated with pesticide residues in apple and banana - Govinda Bhandari; Anushka Pandey; Saima Arif; Sheelendra Pratap Singh (Food Control, 2024)

Remediation of Neonicotinoid Polluted Environment by Silica Hybrid Nanosorbents - Uzaira Rafique; Saima Nasreen; Komal Gul Bangash; Shamyla Nawazish; Qaisar Mahmood (Water, Air, & Soil Pollution, 2024)

Solar light driven degradation of piroxicam and paracetamol by heterogeneous photocatalytic fenton system: Process optimization, mechanistic studies and toxicity assessment - Muhammad Mohsin; Nazia Yaqoob; Shagufta Kamal; Saima Rehman (Chemosphere, 2024)

Biochemical and nutritional analysis of seaweed (Iyengaria stellata) and its therapeutic significance, using antioxidant, antimicrobial, and hypoglycemic activities - Muhammad Imran; Arshad Iqbal; Arwa Abdulkreem AL-Huqail; Suliman Mohammed Suliman Alghanem; Syed Lal Badshah; Saad Alghamdi; Mazen Almehmadi; Uthman Balgith Algopishi; Baber Ali; Saima Sohni; Muhammad Ammar Javed; Doaa Bahaa Eldin Darwish (South African Journal of Botany, 2024)

MEC is Associated With Feeding Practices and Children's Dietary Intake in Family Child Care Homes: A Validation Study - Jasmin Smith; Dipti Dev; Saima Hasnin; Carly Hillburn; Kaung Nyi; Natalie Koziol; Jaclyn Saltzman; Susan Sisson (Journal of Nutrition Education and Behavior, 2024)

Five Himalayan weeds as potential bioresources for bioactive agents: toxic compounds to valuable scaffolds - Ekta Bala; Varun Aggarwal; Pawan Kumar; Rohit Sharma; Saima; Manickam Selvaraj; Mohammed A. Assiri; Praveen Kumar Verma (Phytochemistry Reviews, 2024)

Retraction Note: Roflumilast Reduces Pathological Symptoms of Sporadic Alzheimer’s Disease in Rats Produced by Intracerebroventricular Streptozotocin by Inhibiting NF-κB/BACE-1 Mediated Aβ Production in the Hippocampus and Activating the cAMP/BDNF Signalling Pathway - Noorul Hasan; Saima Zameer; Abul Kalam Najmi; Suhel Parvez; Mohd Akhtar (Neurotoxicity Research, 2024)

Exploring the dynamical bifurcation and stability analysis of Nipah virus; novel perspectives utilizing fractional calculus - Sehrish Ramzan; Saima Rashid; Muzamil Abbas Shah; Sayed K. Elagan (Modeling Earth Systems and Environment, 2024)

Monitoring of environmental persistent organic pollutants in hair samples of cats and dogs - Oguzhan Yavuz; Handan Hilal Arslan; Orhan Tokur; Ozge Marangoz; Zeyno Nuhoglu Ozturk; Saima Mushtaq (Science of The Total Environment, 2024)

Smart colorimetric indicator films prepared from chitosan and polyvinyl alcohol with high mechanical strength and hydrophobic properties for monitoring shrimp freshness - Jehangir Khan; Haoyue An; Shah Alam; Saima Kalsoom; Shu Huan Chen; Teshale Ayano Begeno; Zhenxia Du (Food Chemistry, 2024)

Seismic evaluation of non-seismically detailed RC buildings in Pakistan: performance and damage accumulation under repeated earthquakes - Saima Munir; Fawad Ahmed Najam; Asad ur Rahman; Umair Jalil Malik; Irfan Ahmad Rana; Ather Ali (Bulletin of Earthquake Engineering, 2024)

Recent advances in the biosynthesis, bioavailability, toxicology, pharmacology, and controlled release of citrus neohesperidin - Saima Akhter; Md. Saiful Islam Arman; Mohammed Abu Tayab; Mohammad Nazmul Islam; Jianbo Xiao (Critical Reviews in Food Science and Nutrition, 2024)

Integrated AI-driven optimization of Fenton process for the treatment of antibiotic sulfamethoxazole: Insights into mechanistic approach - Saima Gul; Sajjad Hussain; Hammad Khan; Muhammad Arshad; Javaid Rabbani Khan; Artur de Jesus Motheo (Chemosphere, 2024)

Synthesis of polymeric ferrite composites (Ni-CoFe2O4/Chitosan, Zn-NiFe2O4/Starch, Co-NiZnFe2O4/Polyaniline, Ni doped CrZnFe2O4/Alginate, and Cr doped ZnCoFe2O4/PVA) for the removal of reactive golden yellow-160 dye from wastewater - Ghulam Mustafa; Ruba Munir; Bushra Sadia; Fazila Younas; Murtaza Sayed; Amna Muneer; Muhammad Fahad Sardar; Gadah Albasher; Saima Noreen (Journal of Environmental Chemical Engineering, 2024)

Jet fuel production via palm oil hydrodeoxygenation over bifunctional zeolite mixture supported Ni catalyst: Effect of Si/Al ratio - Saima Khan; Khan Muhammad Qureshi; Zeng Luyao; Andrew Ng Kay Lup; Muhamad Fazly Abdul Patah; Chong Yang Chuah; Wan Mohd Ashri Wan Daud (Biomass and Bioenergy, 2024)

Microplastic (MP) Pollution: Environmental Fate, Eco-toxicity and Sustainable Remediation - Muneeb U. Rehman; Showkat Ul Nabi; Ali Mohd Yatoo; Shafat Ali; Aamir Ahmad Raina; Iqra Hussain; Summya Rashid; Saima Mushtaq; Mubashir Hussain Masoodi (Water, Air, & Soil Pollution, 2024)

Construction and Utilization of Innovative Zeolite/Perovskite/Graphene Oxide, Zeolite/Chitosan/Graphene Oxide, and Zeolite/Biochar/Graphene Oxide Nanohybrid Composites for Adsorptive Remediation of Cationic Dye from Wastewater - Nageen Mushtaq; Ruba Munir; Muhammad Zia-ur-Rehman; Zia ul-Haq; Muhammad Zeeshan Bashir; Amna Muneer; Hina Ambreen; Saima Noreen (Water Conservation Science and Engineering, 2024)

Assessment of textile effluent treatment by immobilized Trametes pubescens MB 89 for plant growth promotion - Uroosa Ejaz; Saima Zakir; Zainul Abideen; Bushra Fahim; Waniya Shaikh; Faryal Shakil; Fizza Haroon Mirza; Syed Wasi Haider; Adnan Khan; Muhammad Sohail (Environmental Science and Pollution Research, 2024)

GCMS and HPLC profiling, antioxidant and anti-inflammatory activities of Crotalaria medicaginea Lamk - Shabana Kusar; Zeb Saddiqe; Faiza Ali; Saima Bashir; Tehzeeb Zubairi (South African Journal of Botany, 2024)

Advancing groundwater vulnerability assessment in Bangladesh: a comprehensive machine learning approach - Saima Sekander Raisa; Showmitra Kumar Sarkar; Md. Ashhab Sadiq (Groundwater for Sustainable Development, 2024)

Exploring zeolite-based composites in adsorption and photocatalysis for toxic wastewater treatment: Preparation, mechanisms, and future perspectives - Iqra Liaquat; Ruba Munir; Naseer Ahmed Abbasi; Bushra Sadia; Amna Muneer; Fazila Younas; Muhammad Fahad Sardar; Muhammad Zahid; Saima Noreen (Environmental Pollution, 2024)

Mixture toxicity of 6PPD-quinone and polystyrene nanoplastics in zebrafish - Shubham Varshney; Olivia L. O'Connor; Adnan Hussain Gora; Saima Rehman; Viswanath Kiron; Prabhugouda Siriyappagouder; Dalia Dahle; Tanja Kögel; Robin Ørnsrud; Pål A. Olsvik (Environmental Pollution, 2024)

Impact of dichromatic lighted incubation on hatching result and post-hatch performance of broiler chickens - Muhammad Faisal Riaz; Athar Mahmud; Jibran Hussain; Saima (Tropical Animal Health and Production, 2024)

Mesenchymal Stromal/Stem Cell Therapy Improves Salivary Flow Rate in Radiation-Induced Salivary Gland Hypofunction in Preclinical in vivo Models: A Systematic Review and Meta-Analysis - Amanda-Louise Fenger Carlander; Anders Kierkegaard Gundestrup; Per Marcus Jansson; Bjarke Follin; Cecilie Hoeeg; Birgitte Saima Kousholt; Rasmus Tolstrup Larsen; Kathrine Kronberg Jakobsen; Susie Rimborg; Anne Fischer-Nielsen; Christian Grønhøj; Christian von Buchwald; et al. (Stem Cell Reviews and Reports, 2024)
Background Mesenchymal stromal/stem cells (MSCs) have been suggested for salivary gland (SG) restoration following radio-induced salivary gland damage. This study aimed to determine the safety and effectiveness of MSC therapy on radio-induced SG damage and hypofunction in preclinical in vivo studies. Methods PubMed and EMBASE were systematically searched for preclinical in vivo interventional studies evaluating efficacy and safety of MSC treatment following radio-induced salivary gland damage published before 10th of January 2022. The primary endpoint was salivary flow rate (SFR) evaluated in a meta-analysis. The study protocol was published and registered on PROSPERO ( www.crd.ac.uk/prospero ), registration number CRD42021227336. Results A total of 16 preclinical in vivo studies were included for qualitative analysis (858 experimental animals) and 13 in the meta-analysis (404 experimental animals). MSCs originated from bone marrow (four studies), adipose tissue (10 studies) and salivary gland tissue (two studies) and were administered intravenously (three studies), intra-glandularly (11 studies) or subcutaneously (one study). No serious adverse events were reported. The overall effect on SFR was significantly increased with a standardized mean difference (SMD) of 6.99 (95% CI: 2.55–11.42). Studies reported improvements in acinar tissue, vascular areas and paracrine factors. Conclusion In conclusion, this systematic review and meta-analysis showed a significant effect of MSC therapy for restoring SG functioning and regenerating SG tissue following radiotherapy in preclinical in vivo studies without serious adverse events. MSC therapy holds significant therapeutic potential in the treatment of radio-induced xerostomia, but comprehensive, randomized, clinical trials in humans are required to ascertain their efficacy in a clinical setting. Graphical Abstract

Biochar imparted constructed wetlands (CWs) for enhanced biodegradation of organic and inorganic pollutants along with its limitation - Ruba Munir; Amna Muneer; Bushra Sadia; Fazila Younas; Muhammad Zahid; Muhammad Yaseen; Saima Noreen (Environmental Monitoring and Assessment, 2024)

Isolation and characterization of novel cadmium-resistant Escherichia fergusonii ZSF-15 from industrial effluent for flocculant production and antioxidant enzyme activity - Saima Zafar; Asma Ashraf; Sumreen Hayat; Muhammad Hussnain Siddique; Muhammad Waseem; Mudassir Hassan; Hira Qaisar; Saima Muzammil (Environmental Monitoring and Assessment, 2024)

Non‐lethal detection of Eubothrium crassum (Cestoda) in farmed Atlantic salmon, Salmo salar , using anal swabs and real‐time PCR - Haakon Hansen; Bjørn Spilsberg; Sigmund Sevatdal; Trine Sakariassen; Christoph Hahn; Saima Nasrin Mohammad; Egil Karlsbakk (Journal of Fish Diseases, 2024)
Detection of intestinal parasites in fish typically requires autopsy, resulting in the sacrifice of the fish. Here, we describe a non‐lethal method for detecting the tapeworm Eubothrium crassum in fish using anal swabs and real‐time PCR detection. Two assays were developed to detect cytochrome oxidase I (COI) mitochondrial DNA and 18S ribosomal DNA sequences of E. crassum , respectively. The assays were tested on swab samples from confirmed pathogen free Atlantic salmon ( Salmo salar L.) and on samples from farmed Atlantic salmon, where the presence and intensity of parasites had been established through autopsy. The COI assay was shown to be specific to E. crassum , while the 18S assay also amplified the closely related E. salvelini , a species infecting Arctic charr ( Salvelinus alpinus L.) in freshwater. The COI assay detected E. crassum in all field samples regardless of parasite load while the 18S assay failed to detect the parasite in two samples. The results thus demonstrates that this non‐lethal approach can effectively detect E. crassum and can be a valuable tool in assessing the prevalence of infection in farmed salmon, aiding in treatment decisions and evaluating treatment effectiveness.

Star anise extract supplementation improved growth performance, hepatic-antioxidant enzyme status, hematology, serum biochemistry, and survival against crowding stress in Catla catla - Wazir Ali; Mahroze Fatima; Syed Zakir Hussain Shah; Noor Khan; Saima Naveed (Aquaculture, 2024)

Lagrangian and Eulerian modelling of river plumes in the Great Barrier Reef system, Australia - Saima Aijaz; Frank Colberg; Gary B. Brassington (Ocean Modelling, 2024)

Unconditional cash transfers, health and savings - Sefa Awaworyi Churchill; Nasir Iqbal; Saima Nawaz; Siew Ling Yew (Economics & Human Biology, 2024)

A computational solution of relativistic Thomas-Fermi equation of an atom with exponential collocation genetic algorithm optimization - Noman Yousaf; Rubina Nasir; Nasir M. Mirza; Saima Rafique (Computer Physics Communications, 2024)

Association Between Arsenic Toxicity, AS3MT Gene Polymorphism and Onset of Type 2 Diabetes - Saima Shokat; Riffat Iqbal; Samreen Riaz; Atif Yaqub (Biological Trace Element Research, 2024)

Health care waste recycling concerning circular economy: a Fermatean fuzzy aggregation operator-based SWARA–MABAC approach - Saima Debbarma; Sayanta Chakraborty; Apu Kumar Saha (Environment, Development and Sustainability, 2024)

Iron Oxide-Chitosan-Based Nanocomposite for Efficient Fluoride Removal From Drinking Water - Suraya Samejo; Jameel Ahmed Baig; Tasneem Gul Kazi; Hassan Imran Afridi; Saima Perveen; Muhammad Umer Frooq; Khalil Akhtar; Shakoor Ahmed Solangi; Fahad Abbasi; Sajjad Hussain (Water, Air, & Soil Pollution, 2024)

MicroRNA: A Novel Micro-machineries to Target Crop Plants for Tolerance to Temperature Stress - Nadia Gul; Javaid Ashraf Nowshehri; Mudasir Ahmad Mir; Saima Wani; Javid I Mir; M. Ashraf Bhat (Plant Molecular Biology Reporter, 2024)

Nickel-induced oxidative stress causes cell death in testicles: implications for male infertility - Saima Parveen; Asim Rizvi; Kafil Akhtar; Aijaz Ahmed Khan; Imrana Naseem (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Evaluation of the Moonlighting Histone H3 Specific Protease (H3ase) Activity and the Dehydrogenase Activity of Glutamate Dehydrogenase (GDH) - Jogeswar Satchidananda Purohit; Madhulika Singh; Yashankita Raghuvanshi; Saima Syeda; Madan M. Chaturvedi (Cell Biochemistry and Biophysics, 2024)

Assessing the impact of renewable energy and financial development on environment quality in Asian emerging economies (AEEs) - Usman Saleem Yousaf; Farhan Ali; Babar Aziz; Shahzad Hussain; Saima Sawar (Environment, Development and Sustainability, 2024)

The genus Neopsittaconirmus (Psocodea: Ischnocera: Philopteridae) from parrots of Pakistan, and evaluation of its distribution on captive parrots (Psittaciformes) around the world - Saima Naz; Oldřich Sychra; Syed Anser Rizvi; Ali Murtaza Dharejo (Research in Veterinary Science, 2024)

Trends and social aspects in the management and conversion of agricultural residues into valuable resources: A comprehensive approach to counter environmental degradation, food security, and climate change - Abbas Sheer; Muhammad Fahad Sardar; Fazila Younas; Pengcheng Zhu; Saima Noreen; Tariq Mehmood; Zia Ur Rahman Farooqi; Sidra Fatima; Weihua Guo (Bioresource Technology, 2024)

Physicochemical characterization of microcrystalline cellulose derived from underutilized orange peel waste as a sustainable resource under biorefinery concept - Saima Sohni; Shehla Begum; Rokiah Hashim; Sher Bahadar Khan; Faryal Mazhar; Fatima Syed; Shahid Ali Khan (Bioresource Technology Reports, 2024)

Melatonin modulates L-arginine metabolism in tumor-associated macrophages by targeting arginase 1 in lymphoma - Anupma Kumari; Saima Syeda; Kavita Rawat; Rani Kumari; Anju Shrivastava (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Assessment and computational bioevaluation of heavy metals from selected cosmetic products - Mishal Zahra; Waqar-Un-Nisa; Luqman Riaz; Saima Kalsoom; Aansa Rukya Saleem; Mehwish Taneez (Environmental Monitoring and Assessment, 2024)

Advanced oxidation/reduction processes (AO/RPs) for wastewater treatment, current challenges, and future perspectives: a review - Qaiser Khan; Murtaza Sayed; Javed Ali Khan; Faiza Rehman; Saima Noreen; Saima Sohni; Ikhtiar Gul (Environmental Science and Pollution Research, 2023)

Co-application of copper nanoparticles and metal tolerant Bacillus sp. for improving growth of spinach plants in chromium contaminated soil - Arslan Ali; Suliman Mohammed Suliman Alghanem; Haifa Abdulaziz Sakit Al-Haithloul; Saima Muzammil; Muhammad Adrees; Effa Irfan; Muhammad Waseem; Alia Anayat; Muhammad Saqalein; Muhammad Rizwan; Shafaqat Ali; Amany H.A. Abeed (Chemosphere, 2023)

Coal fly ash supported Ag@Bi2WO6: A novel heterogeneous nanocomposite for effective sunlight driven photocatalytic degradation of dye - Muhammad Zubair Saleem; Nimra Nadeem; Muhammad Shahbaz; Nabil Al-Zaqri; Shahid Rasul; Saima Noreen; Muhammad Zahid; Imran shahid (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Verification and intercomparison of global ocean Eulerian near-surface currents - Saima Aijaz; Gary B. Brassington; Prasanth Divakaran; Charly Régnier; Marie Drévillon; Jan Maksymczuk; K. Andrew Peterson (Ocean Modelling, 2023)

Proteosomes based on milk phospholipids and proteins to enhance the stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Ramla Shahid; Tayyaba Noor; Muhammad Imran (Food Chemistry, 2023)

Waste Sheep Wool and Its Hydrolysate as a Nutritional Support for Sugar Beet - Hanife Akca; Mehmet Burak Taskin; Murat Tugrul; Saima Kalsoom Babar; Aydin Gunes (Sugar Tech, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Multifunctional nucleoside-AIEgens bearing quaternary ammonium cationic for reversible response, bioimaging, and antibacterial - Yating Zeng; Saima Hameed; Hai Xiong (Analytica Chimica Acta, 2023)

Role of ENPP1 Gene Variants in the Susceptibility to Diabetic Nephropathy in Patients with type 2 Diabetes Mellitus - Niloofar Faraji; Saima Abbaspour; Farzam Ajamian; Parvaneh Keshavarz (Biochemical Genetics, 2023)

Chromium and plant health: A prospective study of toxicity to remediation and restoration of the environment - Mujtaba Aamir Bhat; Awdhesh Kumar Mishra; Saima Jan; Sumreen Amin Shah; Mohd Asgher; Safikur Rahman; Arif Tasleem Jan (South African Journal of Botany, 2023)

Synergistic effect of microwave heating and thermosonication on the physicochemical and nutritional quality of muskmelon and sugarcane juice blend - Pinky Fatima; Muhammad Nadeem; Ashiq Hussain; Tusneem Kausar; Abdul Rehman; Tahira Siddique; Khurram Kabir; Saima Noreen; Rizwan Nisar; Haya Fatima; Sameh A. Korma; Jesus Simal-Gandara (Food Chemistry, 2023)

Co-occurrence of mycotoxins and other fungal metabolites in total mixed rations of cows from dairy farms in Punjab, Pakistan - Felipe Penagos-Tabares; Mubarik Mahmood; Muhammad Zafar Ullah Khan; Hafiz Muhammad Amjad Talha; Muhammad Sajid; Kanwal Rafique; Saima Naveed; Johannes Faas; Juan Ignacio Artavia; Michael Sulyok; Anneliese Müller; Rudolf Krska; et al. (Mycotoxin Research, 2023)
After India and the USA, Pakistan is the third country leading in global dairy production, a sector of very high socioeconomic relevance in Asia. Mycotoxins can affect animal health, reproduction and productivity. This study analysed a broad range of co-occurring mycotoxins and fungal secondary metabolites derived from Alternaria , Aspergillus , Fusarium , Penicillium and other fungal species. To complete this, a validated multi-metabolite liquid chromatography/electrospray ionization-tandem mass spectrometric (LC/ESI–MS/MS) method was employed, detecting 96 of > 500 tested secondary fungal metabolites. This first preliminary study demonstrated that total mixed rations (TMRs) ( n = 30) from big commercial dairy cattle farms (> 200 lactating cows) in Punjab, Pakistan, presented ubiquitous contamination with mixtures of mycotoxins. The mean of mycotoxins per sample was 14, ranging from 11 to 20 mycotoxins among all TMR samples. Metabolites derived from other fungi and Fusarium spp. showed the highest levels, frequency and diversity among the detected fungal compounds. Among the most prevalent mycotoxins were Fusarium toxins like fumonisins B1 (FB1) (93%), B2 (FB2) (100%) and B3 (FB3) (77%) and others. Aflatoxin B1 (AFB1) was evidenced in 40% of the samples, and 7% exceeded the EU maximum limit for feeding dairy cattle (5 µg/kg at 88% dry matter). No other mycotoxin exceeds the EU guidance values (GVs). Additionally, we found that dietary ingredients like corn grain, soybean meal and canola meal were related to increased contamination of some mycotoxins (like FB1, FB2 and FB3) in TMR from the province of Punjab, Pakistan. Among typical forage sources, the content of maize silage was ubiquitous. Individually, the detected mycotoxins represented relatively low levels. However, under a realistic scenario, long-term exposure to multiple mycotoxins and other fungal secondary metabolites can exert unpredictable effects on animal health, reproduction and productivity. Except for ergot alkaloids (73%), all the groups of metabolites (i.e. derived from Alternaria spp., Aspergillus spp., Fusarium spp., Penicillium spp. and other fungi) occurred in 100% of the TMR samples. At individual levels, no other mycotoxins than AFB1 represented a considerable risk; however, the high levels of co-occurrence with several mycotoxins/metabolites suggest that long-term exposure should be considered because of their potential toxicological interactions (additive or synergistic effects).

CYP26B1-related disorder: expanding the ends of the spectrum through clinical and molecular evidence - Karina C. Silveira; Inara Chacon Fonseca; Connor Oborn; Parker Wengryn; Saima Ghafoor; Alexander Beke; Ema S. Dreseris; Cassandra Wong; Aline Iacovone; Carrie-Lynn Soltys; Riyana Babul-Hirji; Osvaldo Artigalas; et al. (Human Genetics, 2023)
CYP26B1 metabolizes retinoic acid in the developing embryo to regulate its levels. A limited number of individuals with pathogenic variants in CYP26B1 have been documented with a varied phenotypic spectrum, spanning from a severe manifestation involving skull anomalies, craniosynostosis, encephalocele, radio-humeral fusion, oligodactyly, and a narrow thorax, to a milder presentation characterized by craniosynostosis, restricted radio-humeral joint mobility, hearing loss, and intellectual disability. Here, we report two families with CYP26B1 -related phenotypes and describe the data obtained from functional studies of the variants. Exome and Sanger sequencing were used for variant identification in family 1 and family 2, respectively. Family 1 reflects a mild phenotype, which includes craniofacial dysmorphism with brachycephaly (without craniosynostosis), arachnodactyly, reduced radioulnar joint movement, conductive hearing loss, learning disability—and compound heterozygous CYP26B1 variants: (p.[(Pro118Leu)];[(Arg234Gln)]) were found. In family 2, a stillborn fetus presented a lethal phenotype with spina bifida occulta, hydrocephalus, poor skeletal mineralization, synostosis, limb defects, and a synonymous homozygous variant in CYP26B1 : c.1083C > A. A minigene assay revealed that the synonymous variant created a new splice site, removing part of exon 5 (p.Val361_Asp382del). Enzymatic activity was assessed using a luciferase assay, demonstrating a notable reduction in exogenous retinoic acid metabolism for the variant p.Val361_Asp382del. (~ 3.5 × decrease compared to wild-type); comparatively, the variants p.(Pro118Leu) and p.(Arg234Gln) demonstrated a partial loss of metabolism (1.7× and 2.3× reduction, respectively). A proximity-dependent biotin identification assay reaffirmed previously reported ER-resident protein interactions. Additional work into these interactions is critical to determine if CYP26B1 is involved with other biological events on the ER. Immunofluorescence assay suggests that mutant CYP26B1 is still localized in the endoplasmic reticulum. These results indicate that novel pathogenic variants in CYP26B1 result in varying levels of enzymatic activity that impact retinoic acid metabolism and relate to the distinct phenotypes observed.

Pollutants in aquatic system: a frontier perspective of emerging threat and strategies to solve the crisis for safe drinking water - Saima Jan; Awdhesh Kumar Mishra; Mujtaba Aamir Bhat; Mudasir Ahmad Bhat; Arif Tasleem Jan (Environmental Science and Pollution Research, 2023)

Ab initio insight into the physical properties of MgXH3 (X = Co, Cu, Ni) lead-free perovskite for hydrogen storage application - Zia ur Rehman; Muhammad Awais Rehman; Bushra Rehman; Surajudeen Sikiru; Saima Qureshi; Esraa Mousa Ali; Muhammad Awais; Mahnoor Amjad; Iqra Iqbal; Anam Rafique; Saira Bibi (Environmental Science and Pollution Research, 2023)

Impact of graded levels of coated calcium butyrate on growth performance and serological indices during pre-weaning stage in Holstein calves - Abdur Rahman; Muhammad Furhan Arshad; Shah Nawaz; Zafar Hayat; Syed Ehtisham ul Haque; Saima Saima; Akhtar Rasool Asif; Muawuz Ijaz; Muhammad Zeeshan Anwar (Tropical Animal Health and Production, 2023)

Epidemiology of pediculosis in the school-going children of district Hyderabad, Sindh, Pakistan - Saima Naz; Maria Rebecca; Ahmad Kamran Khan; Irfan Ahmed (International Journal of Tropical Insect Science, 2023)

Water quality, governance issues, people's perception and water distribution network management through integrated techniques under changing climate - Toqeer Ahmed; Mumtaz Ahmed; Saima Naz; Umair Bin Nisar; Muhammad Zahir (Urban Climate, 2023)

Effect of NDF levels of complete pelleted diet and dietary transition period on rumen pH, growth performance, digestibility, and blood indices in fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Scientific considerations in the regulatory approval of generic (or biosimilar) version of enoxaparin sodium – A lifesaving carbohydrate polymer - Zarina Iqbal; Saima Sadaf (Regulatory Toxicology and Pharmacology, 2023)

Variants in FREM1 and trisomy 18 identified in a neonatal progeria patient - Saima Siddiqi; Noor ul Ain; Mehran Kauser; Zahra Mukhtar; Muhammad Ansar; Muhammad Umair (Molecular Biology Reports, 2023)

Ascorbic acid and salvianolic acid B enhance the valproic acid and 5-azacytidinemediated cardiac differentiation of mesenchymal stem cells - Nukhba Akbar; Hira Anum; Syeda Saima Razzaq; Asmat Salim; Shumaila Usman; Kanwal Haneef (Molecular Biology Reports, 2023)

The Role of Tau Proteoforms in Health and Disease - Zuha Waheed; Jawaria Choudhary; Faria Hasan Jatala; Fatimah; Aneeqa Noor; Inga Zerr; Saima Zafar (Molecular Neurobiology, 2023)

Phosphorus-Enriched Rice Husk Biochar Affected Growth and Mineral Nutrition of Wheat and Its Residual Effects on Maize Production - Ozge Sahin; Aydin Gunes; Saima Kalsoom Babar; Kıymet Deniz; Yusuf Kagan Kadioglu; Sevval Ozturk; Ali Inal (Journal of Soil Science and Plant Nutrition, 2023)

Forewarning of stripe rust (Puccinia striiformis) of wheat in Jammu plains - Sheikh Saima Khushboo; Vishal Gupta; Devanshi Pandit (Indian Phytopathology, 2023)

The importance of public sector size and resources volatility in carbon emissions: Empirical evidence from OECD countries - Qiu Lei; Weiyun Huang; Fang Zhao; Saima Sarwar; Muhammad Gulzaib Chaudhary (Resources Policy, 2023)

Milk phospholipids and buttermilk based composite nanosystems for enhanced stability and bioaccessibility of β-carotene - Bina Zarif; Saima Shabbir; Abdur Rahman; Tauqir A. Sherazi; Ramla Shahid; Tayyaba Noor; Muhammad Imran (International Dairy Journal, 2023)

Insight into crustacean cathepsins: Structure-evolutionary relationships and functional roles in physiological processes - Isma Gul; Muhammad Nadeem Abbas; Saima Kausar; Jili Luo; Xinyue Gao; Yuhang Mu; Wenhui Fan; Honghuan Cui (Fish & Shellfish Immunology, 2023)

Investigating the Spatiotemporal Distributions of NO2, SO2 and Their Association with NDVI in Lahore (Pakistan) and Its Adjoining Region of Punjab (India) - Farrukh Rana; Saima Siddiqui; Zia ul-Haq (Journal of the Indian Society of Remote Sensing, 2023)

Corrigendum to “Ameliorative effect of alendronate against intracerebroventricular streptozotocin induced alteration in neurobehavioral, neuroinflammation and biochemical parameters with emphasis on Aβ and BACE-1” [Neurotoxicology 70 (2019) pp. 122–134] - Saima Zameer; Madhu Kaundal; Divya Vohora; Javed Ali; Abul Kalam Najmi; Mohd Akhtar (NeuroToxicology, 2023)

Criterion Validity of Veggie Meter® to Estimate Fruit and Vegetable Consumption in Non-Hispanic White Preschool Children - Saima Hasnin; Naveta Bhatti; Dipti A. Dev (Journal of Nutrition Education and Behavior, 2023)

A review of the ecosystem services provided by the marine forage fish - Sinan Nissar; Yahya Bakhtiyar; Mohammad Yasir Arafat; Saima Andrabi; Abrar Ahmad Bhat; Tabasum Yousuf (Hydrobiologia, 2023)

Assessment of natural radioactivity levels and potential health risks around coal fired brick kilns of twin cities Rawalpindi and Islamabad, Pakistan - Saima Shaheen; Abdul Jabbar; Syed Zafar Ilyas; Mazzammal Hussain; Muhmmad Dilband; Khizar Hayat Satti; Tahira Shabbir; Khurram Mehboob; Amara Naseem (Arabian Journal of Geosciences, 2023)

Isolation of secondary metabolites from Syzygium aromaticum (L.) Merr. & L.M.Perry. (cloves), and evaluation of their biological activities - Zareena Kiran; Hafiz Nadeem Khan; Saima Rasheed; Sabira Begum; M. Iqbal Choudhary; Sara; Zarina Bano; Bina S. Siddiqui; Shahina Fayyaz; Erum Iqbal; Tooba Hussain; Mehreen Lateef; et al. (Natural Product Research, 2023)

Potential of pectin-chitosan based composite films embedded with quercetin-loaded nanofillers to control meat associated spoilage bacteria - Syed Muhammad Afroz Ali; Taskeen Niaz; Anas Munir; Ramla Shahid; Saima Shabbir; Tayyaba Noor; Muhammad Imran (Food Bioscience, 2023)

Replacing ground Rhodes grass hay with soyhulls in the pelleted diet: effects on ingestive behavior, nutrient digestibility, blood metabolites, growth performance, and economic viability of intensive fattening Lohi lambs - Muhammad Khan; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Imran Mohsin; Habib Ur Rehman (Tropical Animal Health and Production, 2023)

Trapping effect of mangrove and saltmarsh habitats on geochemical elements: a case study in Ximen Island, Zhejiang, China - Saima Sultana; Runqiu Huang; Lukas Van Zwieten; Hailong Wang; Jiaping Wu (Journal of Soils and Sediments, 2023)

Commercial Low Molecular Weight Heparins — Patent Ecosystem and Technology Paradigm for Quality Characterization - Zarina Iqbal; Saima Sadaf (Journal of Pharmaceutical Innovation, 2023)

Morpho-molecular characterisation of angular leaf spot pathogen and identification of new sources of resistance in North-western Himalayan common beans - Saima Gani; Asha Nabi; Parvaze A. Sofi; Tariq. R. Rather; Baby Summuna; Fehim. Jeelani Wani; Mehraj. D. Shah; Bilal A. Padder; Tahir Sheikh; Reyazul Rouf Mir; Aaqif Zaffar; Noor-ul-Ain (Indian Phytopathology, 2023)

Genotype by yield*trait (GYT) biplot analysis: a novel approach for evaluating advance lines of durum wheat - Muhammad Faheem; Saima Mir Arain; Mahboob Ali Sial; Khalil Ahmed Laghari; Abdul Qayyum (Cereal Research Communications, 2023)

In-vitro assessment of a novel plant rhizobacterium, Citrobacter freundii, for degrading and biocontrol of food mycotoxin deoxynivalenol - Bilal Murtaza; Xiaoyu Li; Liming Dong; Muhammad Kashif Saleemi; Mazhar Iqbal; Saima Majeed; Ashiq Ali; Gen Li; Bowen Jin; Lili Wang; Yongping Xu (Toxicon, 2023)

Salt ion mediated changes in biochemical and anatomical characteristics of Brassica napus can be countered with Moringa Leaf extract - Noreen Akhter; Aqsa Noreen; Saima Saifullah; Ali Noman; Muhammad Muslim Shahnaz; Puleng M. Letuma; Abida Kausar; Maham Siddique; Mohamed Hashem; Saad Alamri; Omar Mahmoud Al-zoubi; Muhammad Saleem; et al. (South African Journal of Botany, 2023)

Green metal oxides coated biochar nanocomposites preparation and its utilization in vertical flow constructed wetlands for reactive dye removal: Performance and kinetics studies - Ruba Munir; Khuram Ali; Syed Abbas Zilqurnain Naqvi; Amna Muneer; Muhammad Zeeshan Bashir; Muhammad Aamer Maqsood; Saima Noreen (Journal of Contaminant Hydrology, 2023)

Visible-light induced photocatalytic degradation of estrone (E1) with hexagonal copper selenide nanoflakes in water - Saima Farooq; Rongsheng Cai; James McGettrick; Emmanuel Pean; Matthew Davies; Ahmed S. Al Harrasi; Richard Palmer; Chedly Tizaoui (Process Safety and Environmental Protection, 2023)

Demethylation of CADM1 and SOCS1 using capsaicin in cervical cancer cell line - Mahek Sharan; Meenakshi Jha; Rishima Chandel; Saima Syeda; Runjhun Mathur; Niraj Kumar Jha; Saurabh Kumar Jha; Harsh Goel; Anju Shrivastava; Sushma Chauhan; Sudheer Pamidimarri; Abhimanyu Kumar Jha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Expression of pro-inflammatory cytokines (IL-6 & IL-18) exacerbate the risk of diabetic nephropathy in the Pakistani population - Maha Maqsood; Saima Sharif; Shagufta Naz; Tasnim Farasat; Farkhanda Manzoor; Maqsood Cheema; Muhammad Saqib (Molecular Biology Reports, 2023)

Impact of eco-friendly chemical pretreatment on physicochemical and surface mechanical properties of sustainable lignocellulosic agricultural waste - Muhammad Sulaiman; Fahad Ali Rabbani; Tanveer Iqbal; Mohsin Ali Kazmi; Saima Yasin; M.A. Mujtaba; M.A. Kalam; Fares Almomani (Algal Research, 2023)

Eco-biology, impact, and management of Sorghum halepense (L.) Pers. - Arslan Masood Peerzada; Hafiz Haider Ali; Zarka Hanif; Ali Ahsan Bajwa; Lynda Kebaso; David Frimpong; Nadeem Iqbal; Halima Namubiru; Saima Hashim; Ghulam Rasool; Sudheesh Manalil; Annemieke van der Meulen; et al. (Biological Invasions, 2023)

Accumulation and human health risk assessment of trace elements in two fish species, Cirrhinus mrigala and Oreochromis niloticus, at Tarukri Drain, District Rahimyar Khan, Punjab, Pakistan - Ahmad Manan Mustafa Chatha; Saima Naz; Borhan Mansouri; Amna Nawaz (Environmental Science and Pollution Research, 2023)

Environmental assessment in fine jewelry in the U.S.-Mexico's Paso del Norte region: A qualitative study via X-ray fluorescence spectroscopy - Maricarmen Lerma; Jesús Cantu; Kazi Saima Banu; Jorge L. Gardea-Torresdey (Science of The Total Environment, 2023)

Utilizing rice straw and sugarcane bagasse as low-cost feedstocks towards sustainable production of succinic acid - Dwini Normayulisa Putri; Shabrina Firlyannisa Pratiwi; Meka Saima Perdani; Desy Rosarina; Tania Surya Utami; Muhamad Sahlan; Heri Hermansyah (Science of The Total Environment, 2023)

Insights into the promising prospect of medicinal chemistry studies against neurodegenerative disorders - Md Mominur Rahman; Md Rezaul Islam; Mst Afroza Alam Tumpa; Sheikh Shohag; Shakil khan shuvo; Jannatul Ferdous; Saima Akter Kajol; Abdullah S.M. Aljohani; Waleed Al Abdulmonem; Abdur Rauf; Muthu Thiruvengadam (Chemico-Biological Interactions, 2023)

Synthesis of Metal Hydroxyapatite Nanoparticles and Their Application, Behavior, and Mechanism in the Removal of Cationic Dye Red 3R from Aqueous Media - Ujala Shafqaat; Ruba Munir; Khuram Ali; Muhammad Ahsan; Muhammad Zeeshan Bashir; Saima Noreen (Water, Air, & Soil Pollution, 2023)

Elevated expression of ISY1, APOA-1, SYNE1, MTG1, and MMP10 at HCC initiation: HCC specific protein network involving interactions of key regulators of lipid metabolism, EGFR signaling, MAPK, and splicing pathways - Laila H. Faraj Shaglouf; Maryam Ranjpour; Saima Wajid; Rakesh Tandon; Karisangal Ramaswamy Vasudevan; Swatantra Kumar Jain (Protoplasma, 2023)

The evolution of integrated multi-trophic aquaculture in context of its design and components paving way to valorization via optimization and diversification - Sinan Nissar; Yahya Bakhtiyar; Mohammad Yasir Arafat; Saima Andrabi; Zahoor Ahmad Mir; Niyaz Ali Khan; Seema Langer (Aquaculture, 2023)

Effect of straw particle size in high grain complete pelleted diet on growth performance, rumen pH, feeding behavior, nutrient digestibility, blood and carcass indices of fattening male goats - Muhammad Awais Khurshid; Muhammad Afzal Rashid; Muhammad Shahbaz Yousaf; Saima Naveed; Muhammad Qamer Shahid; Habib Ur Rehman (Small Ruminant Research, 2023)

Improving performance of deep learning predictive models for COVID-19 by incorporating environmental parameters - Roshan Wathore; Samyak Rawlekar; Saima Anjum; Ankit Gupta; Hemant Bherwani; Nitin Labhasetwar; Rakesh Kumar (Gondwana Research, 2023)

Identification, molecular characterization, and pathological features of orf virus in sheep and goats in Punjab province, Pakistan - Irtaza Hussain; Muti ur Rehman Khan; Asim Aslam; Masood Rabbani; Saima Masood; Ahsan Anjum (Tropical Animal Health and Production, 2023)

Biological Control Potential of Endophytic Fungi with Amelioration of Systemic Resistance in Sunflower and GC–MS Metabolic Profiling of Talaromyces assiutensis - Hafiza Farhat; Faizah Urooj; Muhammed Irfan; Nida Sohail; Saima Majeed; Shahid Ullah; Hafza Asma Shafique (Current Microbiology, 2023)

A critical review on the inactivation of surface and airborne SARS-CoV-2 virus by ozone gas - Saima Farooq; Chedly Tizaoui (Critical Reviews in Environmental Science and Technology, 2023)

Natural remedies for Alzheimer’s disease: A systematic review of randomized controlled trials - Saara Ahmad; Saad Bilal Ahmed; Asra Khan; Muhammad Wasim; Saiqa Tabassum; Saida Haider; Fatima Ahmed; Zehra Batool; Saima Khaliq; Hamna Rafiq; Prashant Tikmani; Anwar-ul-Hassan Gilani (Metabolic Brain Disease, 2023)

Efficient photocatalytic degradation of Rhodamine B dye using solar light-driven La˗Mn co-doped Fe2O3 nanoparticles - Sobia Maqbool; Adeel Ahmed; Arif Mukhtar; Muhammad Jamshaid; Aziz Ur Rehman; Saima Anjum (Environmental Science and Pollution Research, 2023)

GIS-based site suitability evaluation for ecotourism development in Salt Range Wetlands, Punjab-Pakistan - Muhammad Ghous; Saima Siddiqui (Arabian Journal of Geosciences, 2022)

Enrichment of trace elements by blue carbon habitats in Maoyan Island of Yueqing Bay, China - Saima Sultana; Runqiu Huang; Yaojia Zhu; Kyaw Thura; Hein Zar Htwe; Li Song; Runjie Jin; Jiali Gu; George Christakos; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2022)

Development of Organically Complexed-Bioaugmented Boron-Coated DAP and Its Effect on Yield and Quality of Canola (Brassica napus L.) - Tayyaba Samreen; Muhammad Imran; Zahir Ahmad Zahir; Muhammad Zulqernain Nazir; Saima Noureen; Safdar Bashir; Sehrish Kanwal; Hassan Munir; Muhammad Aamer Maqsood (Journal of Plant Growth Regulation, 2022)

Water quality and health risk assessment of trace elements in surface water at Punjnad Headworks, Punjab, Pakistan - Saima Naz; Borhan Mansouri; Ahmad Manan Mustafa Chatha; Qudrat Ullah; Zain Ul Abadeen; Muhammad Zahoor Khan; Adnan Khan; Saba Saeed; Rayees Ahmad Bhat (Environmental Science and Pollution Research, 2022)

Recent advances in the therapeutic application of short-chain fatty acids (SCFAs): An updated review - Abdur Rauf; Anees Ahmed Khalil; Ubaid-ur- Rahman; Ahood Khalid; Saima Naz; Mohammad Ali Shariati; Maksim Rebezov; Ewaldo Zavala Urtecho; Ricardo Diego Duarte Galhardo de Albuquerque; Sirajudheen Anwar; Abdulwahab Alamri; Ramesh Kumar Saini; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Using plasma proteomics to investigate viral infections of the central nervous system including patients with HIV-associated neurocognitive disorders - Saima Ahmed; Arthur Viode; Patrick van Zalm; Judith Steen; Shibani S. Mukerji; Hanno Steen (Journal of NeuroVirology, 2022)

Impact of spatio-temporal land surface temperature on cropping pattern and land use and land cover changes using satellite imagery, Hafizabad District, Punjab, Province of Pakistan - Aqil Tariq; Saima Siddiqui; Alireza Sharifi; Syed Hassan Iqbal Ahmad Shah (Arabian Journal of Geosciences, 2022)

Livestock impacts on an iconic Namib Desert plant are mediated by abiotic conditions - Jeffrey T. Kerby; Flora E. Krivak-Tetley; Saima D. Shikesho; Douglas T. Bolger (Oecologia, 2022)
Resolving the relative contributions of top-down versus bottom-up drivers of vegetation dynamics is a major challenge in drylands. In the coming decades, growing livestock populations and shifts in water availability will simultaneously impact many arid systems, but a lack of empirical data on plant responses to these pressures limits understanding of how plants will respond. Here, we combine ground and drone observations from an herbivore exclosure experiment to identify ungulate visitation patterns and their impacts on the cover and melon production of !nara ( Acanthosicyos horridus ), a large, long-lived desert plant in the hyper-arid Namib Desert. !Nara are of key ecological, social, and economic importance to Namib ecosystems and to the local Topnaar people. At our study site, we find that among native and domestic herbivores, free-ranging donkeys have the largest impact on !nara cover and melon production. !Nara cover was negatively affected by herbivores close to the desert-ephemeral river ecotone during a dry period, whereas !nara cover increased on all plants across the landscape during a wetter period, regardless of herbivore access. !Nara near the river channel and those protected from herbivores had more mature melons, particularly during the wetter period. At this site, the potential for conflict between Topnaar !nara melon harvesting and pastoral practices varies with a plant’s distance from the river and prevailing abiotic conditions. This work advances monitoring approaches and adds empirical support to the understanding that top-down and bottom-up regulation of plant dynamics varies with spatiotemporal context, even within landscapes.

Exploring environment sensitivity to fiscal and monetary policies in China: using ecological footprints as a contemporary proxy - Usman Saleem Yousaf; Farhan Ali; Shabib Haider Syed; Babar Aziz; Saima Sarwar (Environmental Science and Pollution Research, 2022)

What causes environmental degradation in Pakistan? Embossing the role of fossil fuel energy consumption in the view of ecological footprint - Usman Saleem Yousaf; Farhan Ali; Babar Aziz; Saima Sarwar (Environmental Science and Pollution Research, 2022)

LC-MS/MS based appraisal of multi-mycotoxin co-occurrence in poultry feeds from different regions of Punjab, Pakistan - Asifa Sarwat; Waqar Rauf; Saima Majeed; Marthe De Boevre; Sarah De Saeger; Mazhar Iqbal (Food Additives & Contaminants Part B-Surveillance, 2022)

Population Index and Growth Estimation Based On SLW Index of the Sea Cucumber (Holothuria arguinensis Koehler & Vaney, 1906) in the Moroccan Waters of the Atlantic Coast - Imane HADDI; Fatiha BENZHA; Mehdi MAANAN; Saima SIDDIQUE; Hassan RHINANE; Najib CHAROUKI; Hakima ZIDANE (Thalassas: An International Journal of Marine Sciences, 2022)

RETRACTED ARTICLE: Roflumilast Reduces Pathological Symptoms of Sporadic Alzheimer’s Disease in Rats Produced by Intracerebroventricular Streptozotocin by Inhibiting NF-κB/BACE-1 Mediated Aβ Production in the Hippocampus and Activating the cAMP/BDNF Signalling Pathway - Noorul Hasan; Saima Zameer; Abul Kalam Najmi; Suhel Parvez; Mohd Akhtar (Neurotoxicity Research, 2022)

Cash transfer program and willingness to pay for environmental services among the ultra-poor in Pakistan - Saima Nawaz; Fatima Gul (Environmental Science and Pollution Research, 2022)

Regional model of foF2 for Pakistan using empirical orthogonal function technique - Uzma Ashraf; Fozia Hanif; Saima Ashraf (Arabian Journal of Geosciences, 2022)

Genetic dissection of grain yield traits in a large collection of spring wheat (Triticum aestivum L.) germplasm - Sultan Habibullah Khan; Muhammad Sajjad; Saima Gulnaz; Sundas Waqar; Munawar Shahzad; Saima Mir Arain (Journal of Crop Science and Biotechnology, 2022)

Comparative genomic analyses of Bacillus subtilis strains to study the biochemical and molecular attributes of nattokinases - Rohit Kapoor; Sapna Khowal; Bibhu Prasad Panda; Saima Wajid (Biotechnology Letters, 2022)

Spatial distribution of hydrochemistry and characterization of groundwater of taluka Bakrani, Larkana, Sindh, Pakistan - Muhammad Farooque Lanjwani; Muhammad Yar Khuhawar; Taj Muhammad Jahangir Khuhawar; Saima Qayoom Memon; Muhammad Soomar Samtio; Abdul Hameed Lanjwani; Imran Khan Rind (Arabian Journal of Geosciences, 2022)

Design, synthesis, in vitro evaluation, and docking studies on ibuprofen derived 1,3,4-oxadiazole derivatives as dual α-glucosidase and urease inhibitors - Saima Daud; Obaid-ur-Rahman Abid; Asma Sardar; Basit Ali Shah; Muhammad Rafiq; Abdul Wadood; Mehreen Ghufran; Wajid Rehman; Zain-ul-Wahab; Fatima Iftikhar; Rifhat Sultana; Habiba Daud; et al. (Medicinal Chemistry Research, 2022)

Enhanced ultraviolet-visible photocatalysis of RGO/equaixial geometry TiO2 composites on degradation of organic dyes in water - Jaafar Hasan; Jing Wang; Zhentao Wang; Muhammad Idrees; Saima Batool; Caiwei Zhang; Chuanguang Qin (Environmental Science and Pollution Research, 2022)

Molecular Profiles of Amyloid-β Proteoforms in Typical and Rapidly Progressive Alzheimer’s Disease - Aneeqa Noor; Saima Zafar; Mohsin Shafiq; Neelam Younas; Anna Siegert; Florian A. Mann; Sebastian Kruss; Matthias Schmitz; Hassan Dihazi; Isidre Ferrer; Inga Zerr (Molecular Neurobiology, 2022)
The molecular determinants of atypical clinical variants of Alzheimer’s disease, including the recently discovered rapidly progressive Alzheimer’s disease (rpAD), are unknown to date. Fibrilization of the amyloid-β (Aβ) peptide is the most frequently studied candidate in this context. The Aβ peptide can exist as multiple proteoforms that vary in their post-translational processing, amyloidogenesis, and toxicity. The current study was designed to identify these variations in Alzheimer’s disease patients exhibiting classical (sAD) and rapid progression, with the primary aim of establishing if these variants may constitute strains that underlie the phenotypic variability of Alzheimer’s disease. We employed two-dimensional polyacrylamide gel electrophoresis and MALDI-ToF mass spectrometry to validate and identify the Aβ proteoforms extracted from targeted brain tissues. The biophysical analysis was conducted using RT-QuIC assay, confocal microscopy, and atomic force microscopy. Interactome analysis was performed by co-immunoprecipitation. We present a signature of 33 distinct pathophysiological proteoforms, including the commonly targeted Aβ 40 , Aβ 42 , Aβ 4-42 , Aβ 11-42 , and provide insight into their synthesis and quantities. Furthermore, we have validated the presence of highly hydrophobic Aβ seeds in rpAD brains that seeded reactions at a slower pace in comparison to typical Alzheimer’s disease. In vitro and in vivo analyses also verified variations in the molecular pathways modulated by brain-derived Aβ. These variations in the presence, synthesis, folding, and interactions of Aβ among sAD and rpAD brains constitute important points of intervention. Further validation of reported targets and mechanisms will aid in the diagnosis of and therapy for Alzheimer’s disease.

Wetting Induced Deformation of Soils Triggering Landslides in Pakistan - Saima Riaz; Mamoru Kikumoto; Muhammad Basharat; Andius Dasa Putra (Geotechnical and Geological Engineering, 2021)

Kinetics and thermodynamic studies of organic dyes removal on adsorbent developed from Viola tricolor extract and evaluation of their antioxidant activity - Tayyaba Shahzadi; Saima Sanaullah; Tauheeda Riaz; Maria Zaib; Amina Kanwal; Hifzah Jabeen (Environment, Development and Sustainability, 2021)

Using space–time scan statistic for studying the effects of COVID-19 in Punjab, Pakistan: a guideline for policy measures in regional agriculture - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Shah Fahad; Wajid Nasim; Hafiz Mohkum Hammad; Ghulam Mustafa Shah; Behzad Murtaza; Muhammad Tahir; Saima Parveen (Environmental Science and Pollution Research, 2021)

The role of CDHR3 in susceptibility to otitis media - Scott D. Hirsch; Christina L. Elling; Tori C. Bootpetch; Melissa A. Scholes; Lena Hafrén; Sven-Olrik Streubel; Harold S. Pine; Todd M. Wine; Wasyl Szeremeta; Jeremy D. Prager; Elisabet Einarsdottir; Ayesha Yousaf; et al. (Journal of Molecular Medicine, 2021)

Establishing influence of morphological aspects on microclimatic conditions through GIS-assisted mathematical modeling and field observations - Hemant Bherwani; Saima Anjum; Ankit Gupta; Anju Singh; Rakesh Kumar (Environment, Development and Sustainability, 2021)

Role of modified diet and gut microbiota in metabolic endotoxemia in mice - Iram Liaqat; Arjumand Iqbal Durrani; Urooj Zafar; Saima Rubab; Mehwish Faheem; Muhammad Mubin; Chand Raza; Nauman Aftab (Archives of Microbiology, 2021)

Petrographical and geoengineering characteristics of evaporitic rocks (Abu Dhabi city vicinity, United Arab Emirates) - Hasan Arman; Osman Abdelghany; Mahmoud Abu Saima; Ala Aldahan; Safwan Paramban (Arabian Journal of Geosciences, 2021)

Zebrafish intestinal transcriptome highlights subdued inflammatory responses to dietary soya bean and efficacy of yeast β‐glucan - Saima Rehman; Adnan H. Gora; Prabhugouda Siriyappagouder; Sylvia Brugman; Jorge M. O. Fernandes; Jorge Dias; Viswanath Kiron (Journal of Fish Diseases, 2021)
Anti‐nutritional factors in dietary components can have a negative impact on the intestinal barrier. Here, we present soya bean‐induced changes in the intestine of juvenile zebrafish and the effect of yeast β‐glucan through a transcriptomic approach. The inclusion of soya bean meal affected the expression of several intestinal barrier function‐related genes like arl4ca , rab25b , rhoub , muc5ac , muc5d , clcn2c and cltb in zebrafish. Several metabolic genes like cyp2x10.2 , cyp2aa2 , aldh3a2b , crata , elovl4 , elovl6 , slc51a , gpat2 and ATP‐dependent peptidase activity ( lonrf , clpxb ) were altered in the intestinal tissue. The expression of immune‐related genes like nlrc3 , nlrp12 , gimap8 , prdm1 and tph1a , and genes related to cell cycle, DNA damage and DNA repair (e.g. spo11 , rad21l1 , nabp1b , spata22 , tdrd9 ) were also affected in the soya bean fed group. Furthermore, our study suggests the plausible effect of yeast β‐glucan through the modulation of several genes that regulate immune responses and barrier integrity. Our findings indicate a subdued inflammation in juvenile zebrafish fed soya bean meal and the efficacy of β‐glucan to counter these subtle inflammatory responses.

Elevated expression of sepiapterin reductase, regulator of G protein signaling 1, hypothetical protein CXorf58 homolog, and zinc finger and BTB domain–containing protein 21 isoform X2 is associated with progression of hepatocellular carcinoma - Maryam Ranjpour; Saima Wajid; Swatantra Kumar Jain (Protoplasma, 2021)

Deciphering the impact of novel coronavirus pandemic on agricultural sustainability, food security, and socio-economic sectors—a review - Mehvish Mumtaz; Nazim Hussain; Zulqarnain Baqar; Saima Anwar; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Correction to: Evaluation of lifestyle risk factor differences in global patterns of breast cancer mortality and DALYs during 1990–2017 using hierarchical age-period-cohort analysis - Sumaira Mubarik; Xiaoxue Liu; Saima Shakil Malik; Lijun Wang; Yong Yu; Chuanhua Yu (Environmental Science and Pollution Research, 2021)

Evaluation of lifestyle risk factor differences in global patterns of breast cancer mortality and DALYs during 1990–2017 using hierarchical age-period-cohort analysis - Sumaira Mubarik; Xiaoxue Liu; Saima Shakil Malik; Lijun Wang; Yong Yu; Chuanhua Yu (Environmental Science and Pollution Research, 2021)

Air pollution and child health: the impact of brick kiln pollution on children's cognitive abilities and physical health in Pakistan - Muhammad Nasir; Faiz Ur Rehman; Shabana Kishwar; Saima Bashir; Muhammad Adil (Environment, Development and Sustainability, 2021)

Experimental Calculations of Metals Content in Skin-Whitening Creams and Theoretical Investigation for Their Biological Effect Against Tyrosinase Enzyme - Tanzeela Ashraf; Mehwish Taneez; Saima Kalsoom; Tahira Irfan; Munib Ahmed Shafique (Biological Trace Element Research, 2021)

Association of genetic polymorphism rs2071676 in carbonic anhydrase gene (CA9) with the risk of squamous cell carcinoma of lungs and esophagus - Saima Saleem; Ramsha Khan; Ghulam Haider; Sara Hasan; Faria Fatima; Sitwat Zehra; Abid Azhar (Biologia, 2021)

A review of landslides related to the 2005 Kashmir Earthquake: implication and future challenges - Muhammad Basharat; Muhammad Tayyib Riaz; M. Qasim Jan; Chong Xu; Saima Riaz (Natural Hazards, 2021)

Mechanism of WASP and WAVE family proteins in the progression of prostate cancer - Mohd Mughees; Faizia Bano; Saima Wajid (Protoplasma, 2021)

Elucidating the Photoluminescence Quenching in Ensulizole: an Artificial Water Soluble Sunscreen - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Saba Shahrum; Shanila Zahra; Saima Shabbir; Azhar Iqbal (Journal of Fluorescence, 2021)

Vitamin D supplementation does not enhance resistance training-induced gains in muscle strength and lean body mass in vitamin D deficient young men - Lauri Savolainen; Saima Timpmann; Martin Mooses; Evelin Mäestu; Luule Medijainen; Lisette Tõnutare; Frederik Ross; Märt Lellsaar; Eve Unt; Vahur Ööpik (European Journal of Applied Physiology, 2021)

RETRACTED ARTICLE: Bi-polymeric Spongy Matrices Through Cross-linking Polymerization: Synthesized and Evaluated for Solubility Enhancement of Acyclovir - Saima Asghar; Naveed Akhtar; Muhammad Usman Minhas; Kifayat Ullah Khan (AAPS PharmSciTech, 2021)

Proximate composition of orange peel, pea peel and rice husk wastes and their potential use as antimicrobial agents and antioxidants - Syeda Andleeb Zahra Naqvi; Ali Irfan; Saima Zaheer; Aeysha Sultan; Shanavas Shajahan; Syeda Laila Rubab; QuratUl Ain; Roberto Acevedo (Vegetos, 2021)

Indigenous wild plants and fungi traditionally used in folk medicine and functional food in District Neelum Azad Kashmir - Shabir Ijaz; Anjum Perveen; Saima Ashraf; Asia Bibi; Yunus Dogan (Environment, Development and Sustainability, 2021)

Petrological control on engineering properties of carbonate rocks in arid regions - Hasan Arman; Osman Abdelghany; Mahmoud Abu Saima; Ala Aldahan; Bahaa Mahmoud; Saber Hussein; Abdel-Rahman Fowler (Bulletin of Engineering Geology and the Environment, 2021)

Estimation of data-driven streamflow predicting models using machine learning methods - Tanveer Ahmed Siddiqi; Saima Ashraf; Sadiq Ali Khan; Muhammad Jawed Iqbal (Arabian Journal of Geosciences, 2021)

Slaking behavior of evaporitic rocks from Abu Dhabi area, United Arab Emirates - Hasan Arman; Osman Abdelghany; Mahmoud Abu Saima; Ala Aldahan; Safwan Paramban (Arabian Journal of Geosciences, 2021)

Effects of spray dried yeast (Saccharomyces cerevisiae) on growth performance and carcass characteristics, gut health, cecal microbiota profile and apparent ileal digestibility of protein, amino acids and energy in broilers - Abdul Hanan Khalid; Khalid Saif Ullah; Saima Naveed; Farooq Latif; Talat Naseer Pasha; Iqtidar Hussain; Shafqat Nawaz Qaisrani (Tropical Animal Health and Production, 2021)

Hindcasting of tropical cyclone winds and waves - Stefan Zieger; Diana J. M. Greenslade; Saima Aijaz; Jeffrey D. Kepert; Andrew Burton (Ocean Dynamics, 2021)

A spatial-temporal decomposition of carbon emission intensity: a sectoral level analysis in Pakistan - Muhammad Azam; Saima Nawaz; Zubair Rafiq; Nasir Iqbal (Environmental Science and Pollution Research, 2021)

Pyrethroid exposure: as determinant of CYP1A1 and GSTP1 genetic variations in occupationally exposed Sindh farmers - Iffat Imran; Saima Saleem; Abid Azhar; Sitwat Zehra (Biologia, 2021)

Diversity and distribution of Genus Primula in Kashmir region: an indicator genus of the western Himalayan mountain wetlands and glacial forelands - Saima Khan; Hamayun Shaheen; Shamshad Aziz; Sidra Nasar (Biodiversity and Conservation, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Air pollution aggravating COVID-19 lethality? Exploration in Asian cities using statistical models - Ankit Gupta; Hemant Bherwani; Sneha Gautam; Saima Anjum; Kavya Musugu; Narendra Kumar; Avneesh Anshul; Rakesh Kumar (Environment, Development and Sustainability, 2021)

Understanding COVID-19 transmission through Bayesian probabilistic modeling and GIS-based Voronoi approach: a policy perspective - Hemant Bherwani; Saima Anjum; Suman Kumar; Sneha Gautam; Ankit Gupta; Himanshu Kumbhare; Avneesh Anshul; Rakesh Kumar (Environment, Development and Sustainability, 2021)

Re-use of wasted sludge to treat industrial pollutants - Ru Wang; Li-ping Yu; Bibi Saima Zeb; Lin-jie Yuan; Meng-yu Liu; Lin-jiang Yuan (Water, Air, & Soil Pollution, 2021)

Efficacy of Characterized Prosopis Wood Biochar Amendments in Improving Growth, Nitrogen Use Efficiency, Nitrate Accumulation, and Mineral Content in Cabbage Genotypes - Peer Saffeullah; Neelofer Nabi; M. Burhanuz Zaman; Saima Liaqat; Tariq Omar Siddiqi; Shahid Umar (Journal of Soil Science and Plant Nutrition, 2021)

Cash transfers and residential demand for electricity: insights from BISP, Pakistan - Nasir Iqbal; Saima Nawaz (Environmental Science and Pollution Research, 2021)

Neutrophil-derived granule cargoes: paving the way for tumor growth and progression - Kavita Rawat; Saima Syeda; Anju Shrivastava (Cancer and Metastasis Reviews, 2021)

Chemical signals driving bacterial–fungal interactions - Saima Khalid; Nancy P. Keller (Environmental Microbiology, 2021)
Summary Microorganisms reside in diverse environmental communities where interactions become indispensable due to close physical associations. These interactions are driven by chemical communication among different microbial kingdoms, particularly between fungi and bacteria. Knowledge about these communication signals provides useful information about the nature of microbial interactions and allows predictions of community development in diverse environments. Here, we provide an update on the role of small signalling molecules in fungal–bacterial interactions with focus on agricultural and medicinal environments. This review highlights the range of – and response to – diverse biochemicals produced by both kingdoms with view to harnessing their properties towards drug discovery applications.

Fungal metabolites as anti-diabetic agents: emphasis on PTP1B inhibitors - Mamona Nazir; Muhammad Saleem; Iftikhar Ali; Ghulam Abbas; Najeeb Ur Rehman; Ivan R. Green; Wahid Hussain; Saima Khan; Hidayat Hussain (Phytochemistry Reviews, 2021)

Mechanism of tumour microenvironment in the progression and development of oral cancer - Mohd Mughees; Anindita Sengupta; Sapna Khowal; Saima Wajid (Molecular Biology Reports, 2021)

Toxic effect of some heavy metals on hematology and histopathology of major carp (Catla catla) - Saima Naz; Riaz Hussain; Qudrat Ullah; Ahmad Manan Mustafa Chatha; Ansar Shaheen; Rifat Ullah Khan (Environmental Science and Pollution Research, 2021)

Synthesis, urease inhibition screening and molecular docking studies of piperonal based imine derivatives - Obaid-ur-Rahman Abid; Saima Daud; Asma Sardar; Wajid Rehman; Abdul Wadood; Ashfaq Ur Rehman; Toheed Akhter; Iram Bibi; Zaheer Ahmad; Muhammad Yasir (Medicinal Chemistry Research, 2021)

Correlation of MSH2 exonic deletions and protein downregulation with breast cancer biomarkers and outcome in Pakistani women/patients - Saima Shakil Malik; Sumaira Mubarik; Ayesha Aftab; Ranjha Khan; Nosheen Masood; Muhammad Asif; Razia Bano (Environmental Science and Pollution Research, 2021)

Identification and computational analysis of USH1C, and SLC26A4 variants in Pakistani families with prelingual hearing loss - Muhammad Noman; Shazia A. Bukhari; Sakina Rehman; Muhammad Qasim; Muhammad Ali; Saima Riazuddin; Zubair M. Ahmed (Molecular Biology Reports, 2020)

Protective Effect of 24-Epibrassinolide on Barley Plants Growing Under Combined Stress of Salinity and Potassium Deficiency - Saima Liaqat; Shahid Umar; Peer Saffeullah; Noushina Iqbal; Tariq O. Siddiqi; M. Iqbal R. Khan (Journal of Plant Growth Regulation, 2020)

Biomolecular alterations by chronic sub-lethal exposure of Malathion and Paraquat in Drosophila melanogaster: study on pesticide tolerance in insects - Mohammad Murtaza Mehdi; Mohammad Layqat; Saima Majid (International Journal of Tropical Insect Science, 2020)

Novel loss-of-function mutations in COCH cause autosomal recessive nonsyndromic hearing loss - Kevin T. Booth; Amama Ghaffar; Muhammad Rashid; Luke T. Hovey; Mureed Hussain; Kathy Frees; Erika M. Renkes; Carla J. Nishimura; Mohsin Shahzad; Richard J. Smith; Zubair Ahmed; Hela Azaiez; et al. (Human Genetics, 2020)

Amenability of Indigenous Genotypes of Cabbage to Scavenge and Accumulate Nitrogen: Importance of Staggered Application and Root Morphology - Peer Saffeullah; Saima Liaqat; Neelofer Nabi; Tinu Anand Kain; Tariq Omar Siddiqi; Sayeed Ahmad; Shahid Umar (Journal of Plant Biology, 2020)

Effects of different light durations during incubation on hatching, subsequent growth, welfare, and meat quality traits among three broiler strains - Rao Muhammad Kashif Yameen; Jibran Hussain; Athar Mahmud; Saima (Tropical Animal Health and Production, 2020)

Effects of dietary organic acids on performance, cecal microbiota, and gut morphology in broilers - Kinza Saleem; Saima; Abdur Rahman; Talat Naseer Pasha; Athar Mahmud; Zafar Hayat (Tropical Animal Health and Production, 2020)

A comparative phylogenomic analysis of SARS-CoV-2 strains reported from non-human mammalian species and environmental samples - Aziz Ul-Rahman; Muhammad Abu Bakr Shabbir; Muhammad Waqar Aziz; Saima Yaqub; Asif Mehmood; Muhammad Asif Raza; Muhammad Zubair Shabbir (Molecular Biology Reports, 2020)

The asymmetric effect of tourism, financial development, and globalization on ecological footprint in Turkey - Danish Iqbal Godil; Arshian Sharif; Saima Rafique; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2020)

CC-NBS-LRR, a set of VvCRP markers, can distinguish cultivars with ripe rot resistance to Colletotrichum pathogens in grapevine - Hyun A. Jang; May Moe Oo; Dae-Gyu Kim; Ha-Yeon Yoon; Mi-Reu Kim; Kyo-Sang Lee; Khaing Shwe Zin Thinn; Saima Arif; Jia Guo Geng; Jiyoung Min; Dong Jun Lim; Youn Young Hur; et al. (Horticulture, Environment, and Biotechnology, 2020)

Anti-glycating and anti-oxidant compounds from traditionally used anti-diabetic plant Geigeria alata (DC) Oliv. & Hiern. - Eltayeb Fadul; Arsalan Nizamani; Saima Rasheed; Achyut Adhikari; Sammer Yousuf; Shahida Parveen; Nezhun Gören; Hassan A. Alhazmi; M. Iqbal Choudhary; Asaad Khalid (Natural Product Research, 2020)

Renal amyloidosis: an update on diagnosis and pathogenesis - Nimisha Gupta; Harshdeep Kaur; Saima Wajid (Protoplasma, 2020)

Electrochemical synthesis of novel aluminium oxyhydroxide-decorated MnO2/chitosan nanocomposite with efficient photocatalytic and antibacterial activity - Saima Sultana; Nafees Ahmad; Ees Ahmad; Suhail Sabir; Mohammad Zain Khan (Nanotechnology for Environmental Engineering, 2020)

Correction to: Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Appraisal of disease-modifying potential of amlodipine as an anti-arthritic agent: new indication for an old drug - Sumera Qasim; Alamgeer; Saima Kalsoom; Muhammad Shahzad; Hafiz Muhammad Irfan; Muhammad Shoaib Zafar; Ishfaq Ali Bukhari; Fahim Vohra; Sibtain Afzal (Inflammopharmacology, 2020)

Cardiac toxicity of heavy metals (cadmium and mercury) and pharmacological intervention by vitamin C in rabbits - Shaukat Ali; Zubia Awan; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Siddique Awan; Saima Sharif; Muhammad Irfan; Muhammad Adeeb Khan (Environmental Science and Pollution Research, 2020)

A novel nonsense mutation in NPR2 gene causing Acromesomelic dysplasia, type Maroteaux in a consanguineous family in Southern Punjab (Pakistan) - Saima Mustafa; Zafrin Akhtar; Muhammad Latif; Mubashir Hassan; Muhammad Faisal; Furhan Iqbal (Genes & Genomics, 2020)
Background Acromesomelic dysplasia, type Maroteaux (AMDM) is a rare skeletal dysplasia following autosomal recessive mode of inheritance and characterized by abnormal growth plates, short and abnormal bones in the extremities and spine. Objective Present study was designed to report the molecular basis of AMDM in enrolled consanguineous family from Pakistan. Methods A consanguineous family from Vehari District in Pakistan having multiple siblings suffering from AMDM was enrolled in present study. Whole exome sequencing (WES) approach was adopted to identify causative agent of AMDM. Human full length NPR2 gene and sequence with nonsense mutation was amplified by using Myc-tagged pXN vector and transformed in E. coli DH5α cells to confirm mutation. SDS-PAGE and Western blotting were done to confirm the production of truncated protein. Computational three dimensional structure generation through homology modeling approach was done to compare protein structure between patients and controls. Results WES reveled a nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene leading to premature termination codon in mRNA of NPR2 gene resulting in a truncated protein with 204 amino acid residues that was confirmed by SDS-PAGE and Western blotting. Sanger sequencing confirmed that mutation in all subjects and mutation followed Mendalian pattern of inheritance. Multiple sequence alignment by ClustalW revealed that mutated domain of NPR2 is conserved region. Proetin structure comparison revealed a significant structural part of NPR2 was missing in truncated protein as compared to control. Conclusion We are reporting that a novel nonsense mutation (c.613 C>T, p.R205X) in exon 1 of NPR2 gene is causing AMDM in a consanguineous Pakistani family.

Silybum marianum (milk thistle) improves vancomycin induced nephrotoxicity by downregulating apoptosis - Naila Malkani; Ammara Naeem; Farah Ijaz; Sidra Mumtaz; Saima Ashraf; Muhammad Imran Sohail (Molecular Biology Reports, 2020)

Microbial l-asparaginase: purification, characterization and applications - Faizan Muneer; Muhammad Hussnain Siddique; Farrukh Azeem; Ijaz Rasul; Saima Muzammil; Muhammad Zubair; Muhammad Afzal; Habibullah Nadeem (Archives of Microbiology, 2020)

Single or Combined Applications of Zinc and Multi-strain Probiotic on Intestinal Histomorphology of Broilers Under Cyclic Heat Stress - Muqader Shah; Hafsa Zaneb; Saima Masood; Rifat Ullah Khan; Muhammad Mobashar; Imad Khan; Salahud Din; Muhammad Shoaib Khan; Habib Ur Rehman; Antonella Tinelli (Probiotics and Antimicrobial Proteins, 2020)

Proteomic sift through serum and endometrium profiles unraveled signature proteins associated with subdued fertility and dampened endometrial receptivity in women with polycystic ovary syndrome - Nadia Rashid; Aruna Nigam; S.K. Jain; Samar Husain Naqvi; Saima Wajid (Cell and Tissue Research, 2020)

Biology, ecology and management of Raphanus raphanistrum L.: a noxious agricultural and environmental weed - Lynda Kebaso; David Frimpong; Nadeem Iqbal; Ali Ahsan Bajwa; Halima Namubiru; Hafiz Haider Ali; Zarka Ramiz; Saima Hashim; Sudheesh Manalil; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2020)

Aluminium oxide nanoparticles inhibit EPS production, adhesion and biofilm formation by multidrug resistant Acinetobacter baumannii - Saima Muzammil; Mohsin Khurshid; Iqra Nawaz; Muhammad Hussnain Siddique; Muhammad Zubair; Muhammad Atif Nisar; Muhammad Imran; Sumreen Hayat (Biofouling, 2020)

Vesicular trafficking–related proteins as the potential therapeutic target for breast cancer - Mohd Mughees; Himanshu Chugh; Saima Wajid (Protoplasma, 2020)

Elevated expression of cellular SYNE1, MMP10, and GTPase1 and their regulatory role in hepatocellular carcinoma progression - Laila H. Faraj Shaglouf; Maryam Ranjpour; Saima Wajid; Swatantra Kumar Jain (Protoplasma, 2020)

Correlation of MLH1 polymorphisms, survival statistics, in silico assessment and gene downregulation with clinical outcomes among breast cancer cases - Saima Shakil Malik; Ayisha Zia; Sumaira Mubarik; Nosheen Masood; Sajid Rashid; Alice Sherrard; Muhammad Bilal Khan; Muhammad Tahir Khadim (Molecular Biology Reports, 2020)

Lignocellulosic biomass supported metal nanoparticles for the catalytic reduction of organic pollutants - Kalsoom Akhtar; Fayaz Ali; Saima Sohni; Tahseen Kamal; Abdullah M. Asiri; Esraa M. Bakhsh; Sher Bahadar Khan (Environmental Science and Pollution Research, 2020)

Sneak peek of Hypericum perforatum L.: phytochemistry, phytochemical efficacy and biotechnological interventions - Mohammad Yaseen Mir; Saima Hamid; Azra N. Kamili; Qazi P. Hassan (Journal of Plant Biochemistry and Biotechnology, 2019)

Circulation of multiple subtypes (A, G and CRFs 02_AG) of human immunodeficiency virus type 1 (HIV-1) in selected districts of Punjab province, Pakistan - Saima Yaqub; Tahir Yaqub; Muhammad Zubair Shabbir; Asif Nadeem; Nadia Mukhtar; Firnas Ata Ur Rehman; Aziz-ul Rahman; Muhammad Furqan Shahid; Muzaffar Ali; Tayyebah Sohail; Zarfishan Tahir (Archives of Virology, 2019)

Strength estimation of evaporitic rocks using different testing methods - Hasan Arman; Osman Abdelghany; Mahmoud Abu Saima; Ala Aldahan; Bahaa Mahmoud; Saber Hussein; Abdel-Rahman Fowler; Saaed AlRashdi (Arabian Journal of Geosciences, 2019)

Reproduction of the Sea Urchin Echinometra mathaei (Echinoidea: Echinodermata) Found on Buleji, Rocky Coast, Pakistan, North Arabian Sea - Saima Siddique; Zarrien Ayub (Thalassas: An International Journal of Marine Sciences, 2019)

Experimental investigation of a catastrophic landslide in northern Pakistan - Saima Riaz; Gonghui Wang; Muhammad Basharat; Kaoru Takara (Landslides, 2019)

Variability in the immunogenic preS region of Pakistani hepatitis B virus isolates - Saima Iftikhar; Muhammad Akhtar (VirusDisease, 2019)

Effect of Dietary Supplementation of Zinc and Multi-Microbe Probiotic on Growth Traits and Alteration of Intestinal Architecture in Broiler - Muqader Shah; Hafsa Zaneb; Saima Masood; Rifat Ullah Khan; Saima Ashraf; Arbab Sikandar; Hafiz Faseeh Ur Rehman; Habib Ur Rehman (Probiotics and Antimicrobial Proteins, 2019)

Exploring the multifaceted neuroprotective actions of Emblica officinalis (Amla): a review - Ibraheem Husain; Saima Zameer; Tushar Madaan; Akram Minhaj; Wasim Ahmad; Asif Iqubaal; Abuzer Ali; Abul Kalam Najmi (Metabolic Brain Disease, 2019)

Cadmium induces GAPDH- and- MDH mediated delayed cell aging and dysfunction in Candida tropicalis 3Aer - Zaman Khan; Muhammad Atif Nisar; Saima Muzammil; Saima Zafar; Inga Zerr; Abdul Rehman (Environmental Monitoring and Assessment, 2019)

Comparative analysis of the cytotoxic activity of extracts from different parts of A. absinthium L. on breast cancer cell lines and correlation with active compounds concentration - Mohd Mughees; Mohd Samim; Sayeed Ahmad; Saima Wajid (Plant Biosystems, 2019)

Biological treatment of red bronze dye through anaerobic process - Saima Fazal; Shaobin Huang; Yongqing Zhang; Zahid Ullah; Arshad Ali; Hao Xu (Arabian Journal of Geosciences, 2019)

Analysis of the People–Forests Relationship in Lower Galliyat, Abbottabad Pakistan - Waseem Hayat; Shakeel Ahmad; Imtyaz Hussain; Yongqing Zhang; Saima Fazal; Salman Khan (Small-scale Forestry, 2019)

Counting the beans: quantifying the adoption of improved mungbean varieties in South Asia and Myanmar - Pepijn Schreinemachers; Teresa Sequeros; Saima Rani; Md. Abdur Rashid; Nithya Vishwanath Gowdru; Muhammad Shahrukh Rahman; Mohammed Razu Ahmed; Ramakrishnan Madhavan Nair (Food Security, 2019)

Cerebrospinal Fluid Total and Phosphorylated α-Synuclein in Patients with Creutzfeldt–Jakob Disease and Synucleinopathy - Matthias Schmitz; Anna Villar-Piqué; Franc Llorens; Karin Gmitterová; Peter Hermann; Daniela Varges; Saima Zafar; Paul Lingor; Hugo Vanderstichele; Leentje Demeyer; Erik Stoops; John Q Trojanowski; et al. (Molecular Neurobiology, 2019)

To Estimate Growth Function by the Use of SLW Index in the Sea Cucumber Holothuria arenicola (Holothuroidea: Echinodermata) of Pakistan (Northern Arabian Sea) - Saima Siddique; Zarrien Ayub (Thalassas: An International Journal of Marine Sciences, 2019)

Association analysis and allelic distribution of deletion in CC chemokine receptor 5 gene (CCR5Δ32) among breast cancer patients of Pakistan - Faria Fatima; Saima Saleem; Abdul Hameed; Ghulam Haider; Syed Aqib Ali Zaidi; Madiha Kanwal; Sitwat Zehra; Abid Azhar (Molecular Biology Reports, 2019)

Correction to: Evaluation of hydrochar efficiency for simultaneous removal of diclofenac and ibuprofen from aqueous system using surface response methodology - Tahira Qureshi; Najma Memon; Saima Q. Memon; Handan Yavuz; Abdesadek Lachgar; Adil Denizli (Environmental Science and Pollution Research, 2019)

Evaluation of hydrochar efficiency for simultaneous removal of diclofenac and ibuprofen from aqueous system using surface response methodology - Tahira Qureshi; Najma Memon; Saima Q. Memon; Handan Yavuz; Abdesadek Lachgar; Adil Denizli (Environmental Science and Pollution Research, 2019)

Simultaneous removal of carbon, sulfur, and nitrogen from biological synthetic wastewater: aerobic and anaerobic approach - Saima Fazal; Hao Xu; Xinrong Xu; Shaobin Huang; Yongqing Zhang; Arshad Ali; Waseem Hayat; Yingying You; Xiaodong Du; Zahid Ullah (Arabian Journal of Geosciences, 2019)

An insight into clinical outcome of XPG polymorphisms in breast cancer - Saima Shakil Malik; Sumaira Mubarik; Nosheen Masood; Muhammad Tahir Khadim (Molecular Biology Reports, 2018)

Deep TMS of the insula using the H-coil modulates dopamine release: a crossover [11C] PHNO-PET pilot trial in healthy humans - Saima Malik; Mark Jacobs; Sang-Soo Cho; Isabelle Boileau; Daniel Blumberger; Markus Heilig; Alan Wilson; Zafiris J. Daskalakis; Antonio P. Strafella; Abraham Zangen; Bernard Le Foll (Brain Imaging and Behavior, 2018)

Effects of biochar on growth, photosynthesis, and chromium (Cr) uptake in Brassica rapa L. under Cr stress - Shafaqat Ali; Muhammad Rizwan; Ruqia Bano; Saima Aslam Bharwana; Muhammad Zia ur Rehman; Muhammad Bilal Hussain; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

LC-MS/MS-based determination of chloramphenicol, thiamphenicol, florfenicol and florfenicol amine in poultry meat from the Punjab-Pakistan - Muhammad Imran; Fazal-e- Habib; Saima Majeed; Abdul Tawab; Waqar Rauf; Moazur Rahman; Muhammad Umer; Mazhar Iqbal (Food Additives & Contaminants: Part A, 2018)

Industrial wastewater treatment in internal circulation bioreactor followed by wetlands containing emergent plants and algae - Faiza Gulzar; Qaisar Mahmood; Zulfiqar Ahmad Bhatti; Bibi Saima Zeb; Shahida Shaheen; Tahir Hayat; Naeem Shahid; Tahseen Zeb (World Journal of Microbiology and Biotechnology, 2018)

Applications of FT-NIRS combined with PLS multivariate methods for the detection & quantification of saccharin adulteration in commercial fruit juices - Fazal Mabood; Javid Hussain; Farah Jabeen; Ghulam Abbas; Batoul Allaham; Mohammed Albroumi; Said Alghawi; Saif Alameri; Syed A Gilani; Ahmed Al-Harrasi; Quazi M.I Haq; Saima Farooq (Food Additives & Contaminants: Part A, 2018)

Insulin releasing effect of some pure compounds from Moringa oleifera on mice islets - Rahman M. Hafizur; Kiran Maryam; Abdul Hameed; Lubna zaheer; Samina Bano; Saima Sumbul; Aisha Sana; Rubeena Saleem; Sehrish Naz; Rizwana S. Waraich; Zaheer Ul-Haq; Shaheen Faizi (Medicinal Chemistry Research, 2018)

Assessment of toxic impact of metals on proline, antioxidant enzymes, and biological characteristics of Pseudomonas aeruginosa inoculated Cicer arietinum grown in chromium and nickel-stressed sandy clay loam soils - Saima Saif; Mohammad Saghir Khan (Environmental Monitoring and Assessment, 2018)

Risk Assessment Integrated QbD Approach for Development of Optimized Bicontinuous Mucoadhesive Limicubes for Oral Delivery of Rosuvastatin - Md Noushad Javed; Kanchan Kohli; Saima Amin (AAPS PharmSciTech, 2018)

Validation of α-Synuclein as a CSF Biomarker for Sporadic Creutzfeldt-Jakob Disease - Franc Llorens; Niels Kruse; André Karch; Matthias Schmitz; Saima Zafar; Nadine Gotzmann; Ting Sun; Silja Köchy; Tobias Knipper; Maria Cramm; Ewa Golanska; Beata Sikorska; et al. (Molecular Neurobiology, 2018)

Trichosides A and B, new withanolide glucosides from Tricholepis eburnea - Saima Maher; Shagufta Rasool; Rashad Mehmood; Shagufta Perveen; Rasool Bakhsh Tareen (Natural Product Research, 2018)

Molecular Alterations in the Cerebellum of Sporadic Creutzfeldt–Jakob Disease Subtypes with DJ-1 as a Key Regulator of Oxidative Stress - Waqas Tahir; Saima Zafar; Franc Llorens; Amandeep Singh Arora; Katrin Thüne; Matthias Schmitz; Nadine Gotzmann; Niels Kruse; Brit Mollenhauer; Juan Maria Torres; Olivier Andréoletti; Isidre Ferrer; et al. (Molecular Neurobiology, 2018)

Coinfection with Lichtheimia corymbifera and Aspergillus flavus in an Immune-Competent Patient Mimicking as Pulmonary-Renal Syndrome - Ali Bin Sarwar Zubairi; Farah Idrees; Kauser Jabeen; Saima Kamal; Afia Zafar (Mycopathologia, 2017)

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems - Ali Ahsan Bajwa; Muhammad Javaid Akhter; Nadeem Iqbal; Arslan Masood Peerzada; Zarka Hanif; Sudheesh Manalil; Saima Hashim; Hafiz Haider Ali; Lynda Kebaso; David Frimpong; Halima Namubiru; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Association of IL-1β, IL-1Ra and FABP1 gene polymorphisms with the metabolic features of polycystic ovary syndrome - Nadia Rashid; Aruna Nigam; Pikee Saxena; S. K. Jain; Saima Wajid (Inflammation Research, 2017)

Cytoskeleton-Associated Risk Modifiers Involved in Early and Rapid Progression of Sporadic Creutzfeldt-Jakob Disease - Saima Zafar; Neelam Younas; Nadeem Sheikh; Waqas Tahir; Mohsin Shafiq; Matthias Schmitz; Isidre Ferrer; Olivier Andréoletti; Inga Zerr (Molecular Neurobiology, 2017)

Reduced expression of SETD2 and SNX9 proteins in chemically induced mammary tumorigenesis in Wistar rats: a prognostic histological and proteomic study - Ishfaq Ahmad Ganaie; Samar Husain Naqvi; Swatantra Kumar Jain; Saima Wajid (Protoplasma, 2017)

Effect of Metformin on Adult Hippocampal Neurogenesis: Comparison with Donepezil and Links to Cognition - Sara Ahmed; Zahra Mahmood; Aneela Javed; Shoaib Naiyer Hashmi; Inga Zerr; Saima Zafar; Saadia Zahid (Journal of Molecular Neuroscience, 2017)

Strain-Specific Altered Regulatory Response of Rab7a and Tau in Creutzfeldt-Jakob Disease and Alzheimer’s Disease - Saima Zafar; Neelam Younas; Susana Correia; Mohsin Shafiq; Waqas Tahir; Matthias Schmitz; Isidre Ferrer; Olivier Andréoletti; Inga Zerr (Molecular Neurobiology, 2017)

DEM-based drainage network analysis using steepness and Hack SL indices to identify areas of differential uplift in Emilia–Romagna Apennines, northern Italy - Saima Siddiqui; Doriano Castaldini; Mauro Soldati (Arabian Journal of Geosciences, 2017)

Synthesis, biological activities and docking studies of novel 2,4-dihydroxybenzaldehyde based Schiff base - Shahzad Murtaza; Aadil Abbas; Kiran Iftikhar; Saima Shamim; Muhammad Shoaib Akhtar; Zobia Razzaq; Khadija Naseem; Abdallah Mohamed Elgorban (Medicinal Chemistry Research, 2016)

Eburneolins A and B, new withanolide glucosides from Tricholepis eburnea - Saima Maher; Shagufta Rasool; Rashad Mehmood; Shagufta Perveen; Rasool Bakhsh Tareen (Natural Product Research, 2016)

Physiological and biochemical mechanisms of silicon-induced copper stress tolerance in cotton (Gossypium hirsutum L.) - Shafaqat Ali; Muhammad Rizwan; Najeeb Ullah; Saima Aslam Bharwana; Muhammad Waseem; Muhammad Ahsan Farooq; Ghulam Hasan Abbasi; Mujahid Farid (Acta Physiologiae Plantarum, 2016)

Perspectives of using fungi as bioresource for bioremediation of pesticides in the environment: a critical review - Zahid Maqbool; Sabir Hussain; Muhammad Imran; Faisal Mahmood; Tanvir Shahzad; Zulfiqar Ahmed; Farrukh Azeem; Saima Muzammil (Environmental Science and Pollution Research, 2016)

Magnesium treatment palliates noise-induced behavioral deficits by normalizing DAergic and 5-HTergic metabolism in adult male rats - Saida Haider; Sadia Sadir; Fizza Naqvi; Zehra Batool; Saiqa Tabassum; Saima Khaliq; Lubna Anis; Irfan Sajid; Darakhshan J. Haleem (Metabolic Brain Disease, 2016)

HIF inhibitors for ischemic retinopathies and cancers: options beyond anti-VEGF therapies - Saima Subhani; Divya Teja Vavilala; Mridul Mukherji (Angiogenesis, 2016)

Growth stimulation and management of diseases of ornamental plants using phosphate solubilizing microorganisms: current perspective - Almas Zaidi; Md. Saghir Khan; Ees Ahmad; Saima Saif; Asfa Rizvi; Mohammad Shahid (Acta Physiologiae Plantarum, 2016)

Effect of Prebiotic Galacto-Oligosaccharides on Serum Lipid Profile of Hypercholesterolemics - Arooj Hashmi; Naureen Naeem; Zubair Farooq; Saima Masood; Sanaullah Iqbal; Rahat Naseer (Probiotics and Antimicrobial Proteins, 2016)

Terpenoid and flavonoid spectrum of in vitro cultures of Glycyrrhiza glabra revealed high chemical heterogeneity: platform to understand biosynthesis - Saima Khan; Pankaj Pandotra; Malik Muzafar Manzoor; Manoj Kushwaha; Rajni Sharma; Shreyansh Jain; Ashok Ahuja; Vishal Amancha; Sashi Bhushan; Santosh Kumar Guru; Ajai Prakash Gupta; Ram Vishwakarma; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Mechanisms of silicon-mediated alleviation of drought and salt stress in plants: a review - Muhammad Rizwan; Shafaqat Ali; Muhammad Ibrahim; Mujahid Farid; Muhammad Adrees; Saima Aslam Bharwana; Muhammad Zia-ur-Rehman; Muhammad Farooq Qayyum; Farhat Abbas (Environmental Science and Pollution Research, 2015)

Route of electrochemical oxidation of the antibiotic sulfamethoxazole on a mixed oxide anode - Sajjad Hussain; Saima Gul; Juliana R. Steter; Douglas W. Miwa; Artur J. Motheo (Environmental Science and Pollution Research, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Citric acid enhances the phytoextraction of chromium, plant growth, and photosynthesis by alleviating the oxidative damages in Brassica napus L. - Sehar Afshan; Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Farhat Abbas; Muhammad Ibrahim; Muhammad Aamer Mehmood; Ghulam Hasan Abbasi (Environmental Science and Pollution Research, 2015)

Fulvic acid mediates chromium (Cr) tolerance in wheat (Triticum aestivum L.) through lowering of Cr uptake and improved antioxidant defense system - Shafaqat Ali; Saima Aslam Bharwana; Muhammad Rizwan; Mujahid Farid; Sidra Kanwal; Qasim Ali; Muhammad Ibrahim; Rafaqat Ali Gill; Muhammad Daud Khan (Environmental Science and Pollution Research, 2015)

Arbuscular mycorrhiza increase artemisinin accumulation in Artemisia annua by higher expression of key biosynthesis genes via enhanced jasmonic acid levels - Shantanu Mandal; Shivangi Upadhyay; Saima Wajid; Mauji Ram; Dharam Chand Jain; Ved Pal Singh; Malik Zainul Abdin; Rupam Kapoor (Mycorrhiza, 2015)

Creutzfeldt-Jakob Disease Subtype-Specific Regional and Temporal Regulation of ADP Ribosylation Factor-1-Dependent Rho/MLC Pathway at Pre-Clinical Stage - Saima Zafar; Matthias Schmitz; Neelam Younus; Waqas Tahir; Mohsin Shafiq; Franc Llorens; Isidre Ferrer; Olivier Andéoletti; Inga Zerr (Journal of Molecular Neuroscience, 2015)

The effect of excess copper on growth and physiology of important food crops: a review - Muhammad Adrees; Shafaqat Ali; Muhammad Rizwan; Muhammad Ibrahim; Farhat Abbas; Mujahid Farid; Muhammad Zia-ur-Rehman; Muhammad Kashif Irshad; Saima Aslam Bharwana (Environmental Science and Pollution Research, 2015)

Molecular genetics of MARVELD2 and clinical phenotype in Pakistani and Slovak families segregating DFNB49 hearing loss - Gowri Nayak; Lukas Varga; Claire Trincot; Mohsin Shahzad; Penelope L. Friedman; Iwar Klimes; John H. Greinwald; S. Amer Riazuddin; Ivica Masindova; Milan Profant; Shaheen N. Khan; Thomas B. Friedman; et al. (Human Genetics, 2015)

Impact of acute sodium citrate ingestion on endurance running performance in a warm environment - Ivi Vaher; Saima Timpmann; Martin Aedma; Vahur Ööpik (European Journal of Applied Physiology, 2015)

Appraisal of active deformation from drainage network and faults: inferences from non-linear analysis - Saima Siddiqui; Mauro Soldati; Doriano Castaldini (Earth Science Informatics, 2015)

Characteristic CSF Prion Seeding Efficiency in Humans with Prion Diseases - Maria Cramm; Matthias Schmitz; André Karch; Saima Zafar; Daniela Varges; Eva Mitrova; Bjoern Schroeder; Alex Raeber; Franziska Kuhn; Inga Zerr (Molecular Neurobiology, 2015)

Short term cadmium administration dose dependently elicits immediate biochemical, neurochemical and neurobehavioral dysfunction in male rats - Saida Haider; Lubna Anis; Zehra Batool; Irfan Sajid; Fizza Naqvi; Saima Khaliq; Shoaib Ahmed (Metabolic Brain Disease, 2015)

Dietary sodium citrate supplementation does not improve upper-body anaerobic performance in trained wrestlers in simulated competition-day conditions - Martin Aedma; Saima Timpmann; Vahur Ööpik (European Journal of Applied Physiology, 2015)

In vitro characterization and pharmacodynamic evaluation of furosemide loaded self nano emulsifying drug delivery systems (SNEDDS) - Pankajkumar Yadav; Ekta Yadav; Amita Verma; Saima Amin (Journal of Pharmaceutical Investigation, 2014)

Effect of Ascorbic Acid on the Degradation of Cyanocobalamin and Hydroxocobalamin in Aqueous Solution: A Kinetic Study - Iqbal Ahmad; Kiran Qadeer; Saima Zahid; Muhammad Ali Sheraz; Tehmina Ismail; Waqar Hussain; Izhar Ahmad Ansari (AAPS PharmSciTech, 2014)

EDTA ameliorates phytoextraction of lead and plant growth by reducing morphological and biochemical injuries in Brassica napus L. under lead stress - Urooj Kanwal; Shafaqat Ali; Muhammad Bilal Shakoor; Mujahid Farid; Sabir Hussain; Tahira Yasmeen; Muhammad Adrees; Saima Aslam Bharwana; Farhat Abbas (Environmental Science and Pollution Research, 2014)

Anchorless 23–230 PrPC Interactomics for Elucidation of PrPC Protective Role - Saima Zafar; Abdul R. Asif; Sanja Ramljak; Waqas Tahir; Matthias Schmitz; Inga Zerr (Molecular Neurobiology, 2014)

Arabidopsis thaliana NAC083 protein interacts with Mungbean yellow mosaic India virus (MYMIV) Rep protein - Geetika Suyal; Vipin Singh Rana; Sunil Kumar Mukherjee; Saima Wajid; Nirupam Roy Choudhury (Virus Genes, 2014)

Potential Use of Low-Cost Lignocellulosic Waste for the Removal of Direct Violet 51 from Aqueous Solution: Equilibrium and Breakthrough Studies - Sana Sadaf; Haq Nawaz Bhatti; Sana Nausheen; Saima Noreen (Archives of Environmental Contamination and Toxicology, 2014)

A non-ionic surfactant reduces the induction time and enhances expression levels of bubaline somatotropin in Pichia pastoris - Saima Sadaf; Hammad Arshad; M. Waheed Akhtar (Molecular Biology Reports, 2014)

Rice Bran: A Novel Functional Ingredient - Mian Kamran Sharif; Masood Sadiq Butt; Faqir Muhammad Anjum; Saima Hafiz Khan (Critical Reviews in Food Science and Nutrition, 2014)

The Saharan isolate Saccharothrix algeriensis NRRL B-24137 induces systemic resistance in Arabidopsis thaliana seedlings against Botrytis cinerea - Saima Muzammil; Clotilde Graillon; Rayenne Saria; Florence Mathieu; Ahmed Lebrihi; Stéphane Compant (Plant and Soil, 2014)

Hydrogen sulfide ameliorates lead-induced morphological, photosynthetic, oxidative damages and biochemical changes in cotton - Saima Aslam Bharwana; Shafaqat Ali; Muhammad Ahsan Farooq; Basharat Ali; Naeem Iqbal; Farhat Abbas; Muhammad Sajid Aqeel Ahmad (Environmental Science and Pollution Research, 2014)

In vitro and in silico exploration of IL-2 inhibition by small drug-like molecules - Saima Kalsoom; Umer Rashid; Awais Shaukat; Omer Mohamed Abdalla; Khalida Hussain; Waqasuddin Khan; Samina Nazir; Mohammad Ahmad Mesaik; Zaheer-ul-Haq; Farzana Latif Ansari (Medicinal Chemistry Research, 2013)

Retention studies of chromium (VI) from aqueous solution on the surface of a novel carbonaceous material - Sajjad Hussain; Saima Gul; Sabir Khan; Habib ur Rehman (Arabian Journal of Geosciences, 2013)

Visualization of grapevine root colonization by the Saharan soil isolate Saccharothrix algeriensis NRRL B-24137 using DOPE-FISH microscopy - Stéphane Compant; Saima Muzammil; Ahmed Lebrihi; Florence Mathieu (Plant and Soil, 2013)

Pharmacophore model generation for microtubule-stabilizing anti-mitotic agents (MSAAs) against ovarian cancer - Asma Abro; Saima Kulsoom; Naveeda Riaz (Medicinal Chemistry Research, 2013)

Use of beneficial bacteria and their secondary metabolites to control grapevine pathogen diseases - Stéphane Compant; Günter Brader; Saima Muzammil; Angela Sessitsch; Ahmed Lebrihi; Florence Mathieu (BioControl, 2013)

Spirulina: possible pharmacological evaluation for insulin-like protein - Razique Anwer; Anzar Alam; Saima Khursheed; Shaikh Mohd. Kashif; Hifzul Kabir; Tasneem Fatma (Journal of Applied Phycology, 2013)

Alteration in plasma corticosterone levels following long term oral administration of lead produces depression like symptoms in rats - Saida Haider; Sadia Saleem; Saiqa Tabassum; Saima Khaliq; Saima Shamim; Zehra Batool; Tahira Parveen; Qurat-ul-ain Inam; Darakhshan J. Haleem (Metabolic Brain Disease, 2013)

In silico ligand-based pharmacophore model generation for the identification of novel Pneumocystis carinii DHFR inhibitors - Yusra Sajid Kiani; Saima Kalsoom; Naveeda Riaz (Medicinal Chemistry Research, 2013)

Identification of an antiepileptic lead compound with a more selective activity and its analogues for GABA-AT using in silico approach - Hina Naz Khan; Saima Kulsoom; Hamid Rashid (Medicinal Chemistry Research, 2013)

Two new halocuprates complexes [CuII(1,4,8,11-tetraazacyclotetradecane)][CuICl3] and [H4(1,4,8,11-tetrazacyclotetradecane)][Cu 2 I Cl6]: synthesis, characterizations and biological studies - Mohammed Lachkar; Ilham Halime; Abdoulillah Bezgour; Brahim El Bali; Michal Dusek; Karla Fejfarova; Sadia Siddiq; Bishnu P. Marasini; Shagufta Noreen; Ajmal Khan; Saima Rasheed; M. Iqbal Choudhary (Medicinal Chemistry Research, 2012)

Effects of heat acclimation on endurance capacity and prolactin response to exercise in the heat - Andres Burk; Saima Timpmann; Kairi Kreegipuu; Maria Tamm; Eve Unt; Vahur Ööpik (European Journal of Applied Physiology, 2012)

Diorganotin (IV) derivative of 2-thiophene acetic acid: characterizations and biological activities of {[n-Bu2SnO2C–CH2–C4H3S]2O}2 - Abdelkader Ettouhami; Abderrahman Yahyi; Abdellah El Mejdoubi; Brahim El Bali; Sadia Siddiq; Sagufta Noureen; Bishnu P. Marasini; Ajmal Khan; Saima Rasheed; M. Iqbal Choudhary (Medicinal Chemistry Research, 2012)

In silico pharmacophore model generation for the identification of novel butyrylcholinesterase inhibitors against Alzheimer’s disease - Sumra Wajid Abbasi; Saima Kulsoom; Naveeda Riaz (Medicinal Chemistry Research, 2012)

In silico studies on 2,3-dihydro-1,5-benzothiazepines as cholinesterase inhibitors - Farzana Latif Ansari; Saima Kalsoom; Zaheer-ul-Haq; Zahra Ali; Farukh Jabeen (Medicinal Chemistry Research, 2012)

Leaf structural modifications for drought tolerance in some differentially adapted ecotypes of blue panic (Panicum antidotale Retz.) - Mansoor Hameed; Saima Batool; Nargis Naz; Tahira Nawaz; Muhammad Ashraf (Acta Physiologiae Plantarum, 2012)

Antimicrobial activity of the methanolic bark extract of Holarrhena pubescens (Buch. Ham), its fractions and the pure compound conessine - Bina S. Siddiqui; Syed Tahir Ali; Ghazala H. Rizwani; Sabira Begum; Saima Tauseef; Aqeel Ahmad (Natural Product Research, 2012)

Detection of immunoactive insulin in Spirulina - Razique Anwer; Saima Khursheed; Tasneem Fatma (Journal of Applied Phycology, 2012)

An efficient anticancer histone deacetylase inhibitor and its analogues for human HDAC8 - Nighat Noureen; Hamid Rashid; Saima Kalsoom (Medicinal Chemistry Research, 2012)

RETRACTED ARTICLE: Bovine viral diarrhea virus nonstructural protein 5A is phosphorylated by cdc2 cyclin-dependent kinase in vitro - Muhammad Atif Zahoor; Saima Naim; Guangai Xue; Mariluz Arainga Ramirez (Archives of Virology, 2012)

Antimycobacterial and antioxidant activities of reserpine and its derivatives - Sabira Begum; Syeda Qamar Zehra Naqvi; Aqeel Ahmed; Saima Tauseef; Bina Shaheen Siddiqui (Natural Product Research, 2012)

A molecular approach to combat spatio-temporal variation in insecticidal gene (Cry1Ac) expression in cotton - Allah Bakhsh; Saima Siddique; Tayyab Husnain (Euphytica, 2012)

Mutations of GIPC3 cause nonsyndromic hearing loss DFNB72 but not DFNB81 that also maps to chromosome 19p - Atteeq U. Rehman; Khitab Gul; Robert J. Morell; Kwanghyuk Lee; Zubair M. Ahmed; Saima Riazuddin; Rana A. Ali; Mohsin Shahzad; Ateeq-ul Jaleel; Paula B. Andrade; Shaheen N. Khan; Saadullah Khan; et al. (Human Genetics, 2011)

Identification of the deleterious 2080insA BRCA1 mutation in a male renal cell carcinoma patient from a family with multiple cancer diagnoses from Pakistan - Muhammad U. Rashid; Sidra Gull; Saima Faisal; Saba Khaliq; Kashif Asghar; Neelam Siddiqui; Asim Amin; Ute Hamann (Familial Cancer, 2011)

Comparative effectiveness of Pseudomonas and Serratia sp. containing ACC-deaminase for coinoculation with Rhizobium leguminosarum to improve growth, nodulation, and yield of lentil - Zahir Ahmad Zahir; Muhammad Zafar-ul-Hye; Saima Sajjad; Muhammad Naveed (Biology and Fertility of Soils, 2011)

Simultaneous Amplification of Two Bacterial Genes: More Reliable Method of Helicobacter pylori Detection in Microbial Rich Dental Plaque Samples - Saima Chaudhry; Muhammad Idrees; Mateen Izhar; Arshad Kamal Butt; Ayyaz Ali Khan (Current Microbiology, 2011)

Quit Smoking for Life—Social Marketing Strategy for Youth: A Case for Pakistan - Liaquat Ali Khowaja; Ali Khan Khuwaja; Parvez Nayani; Saleem Jessani; Malika Parveen Khowaja; Saima Khowaja (Journal of Cancer Education, 2010)

Y chromosomes of self-identified Syeds from the Indian subcontinent show evidence of elevated Arab ancestry but not of a recent common patrilineal origin - Elise M. S. Belle; Saima Shah; Tudor Parfitt; Mark G. Thomas (Archaeological and Anthropological Sciences, 2010)

A study of the chemical composition of black cumin oil and its effect on penetration enhancement from transdermal formulations - Saima Amin; Showkat R. Mir; Kanchan Kohli; Babar Ali; Mohd Ali (Natural Product Research, 2010)

Two new triterpenoid isomers from Nerium oleander leaves - Bina S. Siddiqui; Nasima Khatoon; Sabira Begum; Saima A. Durrani (Natural Product Research, 2009)

Gene structure and mutant alleles of PCDH15: nonsyndromic deafness DFNB23 and type 1 Usher syndrome - Zubair M. Ahmed; Saima Riazuddin; Sandar Aye; Rana A. Ali; Hanka Venselaar; Saima Anwar; Polina P. Belyantseva; Muhammad Qasim; Sheikh Riazuddin; Thomas B. Friedman (Human Genetics, 2008)

The autosomal recessive nonsyndromic deafness locus DFNB72 is located on chromosome 19p13.3 - Quratul Ain; Sabiha Nazli; Saima Riazuddin; Ateeq-ul Jaleel; S. Amer Riazuddin; Ahmad U. Zafar; Shaheen N. Khan; Tayyab Husnain; Andrew J. Griffith; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Inhibitory effect of lactone fractions and individual components from three species of the Achillea millefolium complex of Bulgarian origin on the human neutrophils respiratory burst activity - Muhammad Iqbal Choudhary; Saima Jalil; M. Todorova; A. Trendafilova; B. Mikhova; H. Duddeck; Atta-ur-Rahman (Natural Product Research, 2007)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

DFNB48, a new nonsyndromic recessive deafness locus, maps to chromosome 15q23-q25.1 - Jamil Ahmad; Shaheen N. Khan; Shahid Y. Khan; Khushnooda Ramzan; Saima Riazuddin; Zubair M. Ahmed; Edward R. Wilcox; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2005)

Long-term effects of fluoxetine or vehicle administration during pregnancy on behavioral outcomes in guinea pig offspring - Raphael Vartazarmian; Saima Malik; Glen B. Baker; Patricia Boksa (Psychopharmacology, 2005)

A new locus for nonsyndromic deafness DFNB49 maps to chromosome 5q12.3-q14.1 - Khushnooda Ramzan; Rehan S. Shaikh; Jamil Ahmad; Shaheen N. Khan; Saima Riazuddin; Zubair M. Ahmed; Thomas B. Friedman; Edward R. Wilcox; Sheikh Riazuddin (Human Genetics, 2005)

Investigation of the Greek ancestry of populations from northern Pakistan - Atika Mansoor; Kehkashan Mazhar; Shagufta Khaliq; Abdul Hameed; Sadia Rehman; Saima Siddiqi; Myrto Papaioannou; L. L. Cavalli-Sforza; S. Qasim Mehdi; Qasim Ayub (Human Genetics, 2004)

Nonsyndromic recessive deafness DFNB18 and Usher syndrome type IC are allelic mutations of USHIC - Zubair M. Ahmed; Tenesha N. Smith; Saima Riazuddin; Tomoko Makishima; Manju Ghosh; Sirosh Bokhari; Puthezhath S. Menon; Dilip Deshmukh; Andrew J. Griffith; Sheikh Riazuddin; Thomas B. Friedman; Edward R. Wilcox (Human Genetics, 2002)

Towards a Cre-based recombination system for generating integrated DNA repertoires site-specifically in yeast - Bryn G. Davies; Claire L. Adams; Saima Aijaz; Jonathan P.L. Cox (Biotechnology Letters, 2002)

Novel mutations of MYO15A associated with profound deafness in consanguineous families and moderately severe hearing loss in a patient with Smith-Magenis syndrome - Nikki Liburd; Manju Ghosh; Saima Riazuddin; Sadaf Naz; Shaheen Khan; Zubair Ahmed; Sheikh Riazuddin; Yong Liang; Puthezhath Menon; Tenesha Smith; Ann Smith; Ken-Shiung Chen; et al. (Human Genetics, 2001)

Effect of creatine supplementation during rapid body mass reduction on metabolism and isokinetic muscle performance capacity - Vahur pik; Mati Psuke; Saima Timpmann; Luule Medijainen; Jaan Ereline; Tamara Smirnova (European Journal of Applied Physiology, 1998)

Exclusive asymptomatic neonatal infections by human rotavirus strains having subgroup I specificity and “long” RNA electropherotype - M. Sukumaran; Krishne Gowda; P. P. Maiya; T. P. Srinivas; M. S. Kumar; Saima Aijaz; R. R. Reddy; L. Padilla; H. B. Greenberg; C. D. Rao (Archives of Virology, 1992)